Sulfate-catalyzed denitrifying anaerobic methane oxidation process mediated by Methanobacterium sp. from digestion sludges - Shibo Fu; Wen-Bo Nie; Xin Tan; Xiaoming Wang; Lili Li; Guo-Jun Xie (Water Research, 2026)

Dual-scale flower detection and homography-guided cluster matching for robotic pollination in trellised kiwifruit orchards - Leilei He; Bo Jia; Juncai Huang; Rui Li; Spyros Fountas; Longsheng Fu (Biosystems Engineering, 2026)

Mechanism and parametric analysis on cooperative seismic mitigation of base-isolated structures equipped with negative stiffness amplifying damper based on a distributed parameter model - Qing Lyu; Xianlei Li; Bo Fu; Liangkun Liu; Zhaoyang Zhang (Soil Dynamics and Earthquake Engineering, 2026)

Petrogenesis of the middle Jurassic Luorong syenite and Xishan A-type granite in the southern Qin-Hang belt, South China: Implications for contrasting mixed sources and divergent differentiation pathways - Zheng-Wei Qin; Xi-Yao Li; Wolfgang Siebel; Jian-Ming Fu; Sanzhong Li; You-Yue Lu; Yu-Xiao Yao; Yu-Shuai Yu; Bo Bao (Journal of Asian Earth Sciences, 2026)

Hydrological sensitivity and carbon dynamics during the evolution of a crater lake peatland in Northeast China - Yuefeng Li; Bo Ding; Zhengyu Xia; Yuwen Fu; Jingjing Sun; Zicheng Yu (CATENA, 2026)

Hydrology–topography controls on biomass responses of emergent wetland plants to drought and flooding in a Yangtze River-connected floodplain wetland - Jiawei Shi; Kerun He; Lianlian Xi; Yining Xia; Peng' ao Liu; Zenghui Peng; Hui Fu; Guixiang Yuan; Yonghong Xie; Youzhi Li; Bo Ren (CATENA, 2026)

Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

A salt-tolerant dual-network hydrogel based on tea waste biochar for efficient seawater desalination - Kun-Xiu Liu; Yi-Bin Li; Lei Xu; Cai-Hua Liu; Zhu-Long Yu; Wen-Bo Guo; Ming-Lai Fu; Baoling Yuan (Journal of Environmental Chemical Engineering, 2026)

Diversity of Diaporthe species associated with post-harvest decay on kiwifruit in China - Lu Feng; Yang Lin; Chao Li; Jiatao Xie; Jiasen Cheng; Bo Li; Tao Chen; Daohong Jiang; Yanping Fu (Fungal Biology, 2026)

Efficient fractionation of reed biomass by inorganic salt-driven seawater/ethanolamine pretreatment for fermentable sugars and N-containing lignin - Hao Tong; Meizhen Jiao; Bo Mu; Bin Li; Shihao Su; Yehan Tao; Jinwen Hu; Jian Du; Jie Lu; Chenglong Fu; Haisong Wang (Chemical Engineering Journal, 2026)

Waste akebiae trifoliata-derived WO3 hierarchical tubes efficient detection of ppb-level triethylamine gas at low temperature and application in food freshness detection - Wen-Xiao Li; Jia-Wang Wang; Rui-Long Li; Qiu-Yue Zheng; Bao-Yu Song; Bo-Ya Liu; Li-Xia Zhao; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2026)

Tracing microplastics uptake and translocation in plants using aggregation-induced emission materials - Yang Liu; Siqi Yang; Xia Wang; Wei Du; Nan Fu; Penglin Li; Heng Wei; Fen Zhao; Zijie Qiu; Hao Qiu; Yanxu Zhang; Willie J.G.M. Peijnenburg; et al. (Journal of Hazardous Materials, 2026)

Urinary biomarkers of emerging contaminants in relation to prevalent Parkinson's disease: An exploratory mixture and network toxicology study - Chiqun Shan; Yiming Ge; Junye Bian; Yuli Lin; Bo Fu; Qinru Xiao; Aihua Guo; Mengyan Li; Pan Xu; Yi Chen; Haobo Chen; Shaoyou Lu (Journal of Hazardous Materials, 2026)

Novel Streptomyces sp. SCUT-3 promoter’ and 5’UTR chimeras enhanced its alginate lyase expression for kelp degradation - Jun Dai; Hai-Ning Wang; Can Qin; Peng-Bo Dan; Jun-Jin Deng; Lei Wu; Zhi-Wei Li; Fu-Gen Zhang; Chu-Yan Liang; Ming-Shu Zhang; Xiao-Chun Luo (Chemical Engineering Journal, 2026)

Recognition of kiwifruit pruning position based on vine segmentation and dormant bud detection with their planar distribution - Shuolin Kong; Bo Jia; Qichen Huang; Juncai Huang; Rui Li; Bao Zhou; Xiancun Zhou; Zhenchao Wu; Jinyong Chen; Xiaoxu Sun; Dateng Zheng; Davut Karayel; et al. (Computers and Electronics in Agriculture, 2026)

Retraction notice to “Rapid transition of aerosol optical properties and water-soluble organic aerosols in cold season in Fenwei Plain” [Sci. Total Environ. 829 (2022) 154661] - Aodong Du; Yan Li; Jiaxing Sun; Zhiqiang Zhang; Bo You; Zhijie Li; Chun Chen; Jie Li; Yanmei Qiu; Xingang Liu; Dongsheng Ji; Wenjie Zhang; et al. (Science of The Total Environment, 2026)

Proteomic insights into the combined effects of near-threshold bleaching temperature and prometryn exposure on the coral Galaxea fascicularis - Sichen Li; Yanyu Zhou; Haochen Niu; Weilu Kang; Guowei Fu; Bo Hu; Hongwei Zhao (Marine Environmental Research, 2026)

Corrigendum to ‘Wavelength-dependent photobiomodulation attenuates synovial inflammation in fibroblast-like synoviocytes and a collagenase-induced osteoarthritis model’ [Journal of Photochemistry & Photobiology B: Biology Volume 272 (2025) 113276] - Tianxiang Fan; Peng Xia; Safayet Ahmed; Yuen H. Tsang; Zhi Yao; Deli Wang; Ziyu Chen; Lixiang Xue; Dongquan Shi; Bo Wang; Chi Fai Cheung; Marco Y.C. Pang; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

MFN2-mediated remodelling of ER-mitochondria communication alleviates ochratoxin A-induced hepatocyte ferroptosis by enhancing mitophagy - Zi-Yan Hu; Rui-Qi Liu; Yu-Xuan Ouyang; Ming-Shan Chen; Jia-Xin Wang; Ming Lou; Yi-Feng Huang; Hong-Li Si; Fu-Wei Jiang; Zhuo-Yu Liu; Yi-Bo Wang; Li Wang; et al. (Journal of Hazardous Materials, 2026)

Phosphorus–boron synergistic carbonization/dormancy strategy enables polyurethane foams with aging enhanced fire safety - Shuang Li; Hai-Bo Zhao; Ming-Jun Chen; Lei He; Lin Zhang; Fu-Rong Zeng; Yu-Zhong Wang (Chemical Engineering Journal, 2026)

Analysis of meteorological causes for a spring PM10 pollution episode over Hainan Island, China - Chuan-bo Fu; Li Dan; Jia-xiang Tang; Jin-he Tong (Atmospheric Research, 2026)

Autofocusing-based adaptive SAR pixel offset tracking for high-accuracy landslide deformation retrieval - Menghua Li; Ying Liu; Dong Fan; Mengshi Yang; Weitao Tian; Zhitao Fu; Bo-Hui Tang (Landslides, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

Biochar-assisted copper removal and metabolic responses of Hydrocotyle vulgaris in a hydroponic system: Insights from untargeted metabolomics and computational modeling - Ziyi Lian; Xiaofan Fu; Haoran Yin; Yuxin Li; Lei Zhao; Jing Shang; Tian Gao; Bo Zhang; Chengbin Xu; Runjie Zhang; Fang Ma; Jieting Wu (Journal of Environmental Management, 2026)

Conserved roles of core morphogens in wing formation of the antlion Myrmeleon bore - Wei Dong; YaNan Li; Qiongqiong Zhang; Yuejun Fu; Xu-Bo Zhang (Insect Biochemistry and Molecular Biology, 2026)

Glucosamine sulfate as a dietary supplement in alleviating nicosulfuron-induced ovarian injury - Yafei Miao; Jiali Xu; Jiaqi Chen; Junheng Zhang; Yehai Fu; Ying Yang; Bo Zhou; Ziyang Li; Huan Liu; Yong Ruan (Food Bioscience, 2026)

Indium-doped CuSnO3 perovskite hybrids for chemiresistive CO sensing - Linyan Gu; Yangtao Qian; Yiting Liu; Miao Cheng; Tao Wei; Qianqian Liu; Ruirui Wang; Wanfei Li; Zhenxiao Fu; Haiyang Jiang; Zibo Li; Bo Liu; et al. (Chemical Engineering Journal, 2026)

Ferroptosis mediated by aggregation of Triosephosphate isomerase 1 links cadmium exposure to pulmonary fibrosis - Yishan Yin; Xuehan Jiang; Jiayi Li; Hongxue Yang; Yi Fang; Bo Li; Hongyu Fu; Jingzeng Cai; Ziwei Zhang (Chemico-Biological Interactions, 2026)

Context-dependent links between microbial co-occurrence topology and nitrogen mineralization in two adjacent subalpine Picea asperata stands - Lixia Wang; Haoying Gao; Shuangjia Fu; Lin Xu; Li Zhang; Han Li; Chengming You; Sining Liu; Hongwei Xu; Jiao Li; Bo Tan; Zhenfeng Xu (Plant and Soil, 2026)

Homocysteine-induced bone formation dysfunction reversed by icariin via the AKT/FOXO1 signaling pathway - Suzhen Chao; Yunying Fu; Xinyi Peng; Yili Zhou; Junjie Xia; Ming Chen; Yang Li; Shengyuan Li; Min Shi; Xunli Xia; Bo Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Monoterpenoids from the roots of Paeonia lactiflora Pall. and their neuroprotective activity - Bo Fu; Yi-Qiang Zhang; Jin-Ling Zhang; Si-Yi Wang; Jia-Tong Wu; Juan Pan; Wei Guan; Zhi-Chao Hao; Qing-Shan Chen; Li-Li Zhang; Hai-Xue Kuang; Yan Liu (Natural Product Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Chemical constituents from the stem of Nauclea officinalis and their anti-inflammatory activities - Bo Wen Wan; Ting Wang; Xiong Bo Zhu; Rui Hua Xu; Hao Fu Dai; Wen Li Mei; Fei Wu; Xiao Ying Peng; Sheng Zhuo Huang (Phytochemistry Letters, 2026)

Recyclable hygroscopic hydrogels with dynamic networks enable efficient solar-driven atmospheric water harvesting - Fu-Yao Zhong; Chen-Xi Li; Lu-Bin Zhong; Chao-Yang Guo; George Zheng Chen; Bo Weng; Jun He; Yu-Ming Zheng (Journal of Environmental Chemical Engineering, 2026)

Comparative study on ignition mechanism and intrinsic combustion kinetics between coal and char - Zezheng Shi; Yang Liu; Yongxiao Jia; Jiye Tao; Kuangyu Li; Zhi Wang; Xinyu Wang; Yumin Chen; Bo Yu; Shisen Xu; Dongliang Xu; Xiangping Wang; et al. (Fuel, 2026)

The synergy of active and passive satellite sensors for robust sea-fog detection: A two-stage machine-learning model with constraints from ICOADS - Luyu Yan; Xuehua Fan; Disong Fu; Hongrong Shi; Lin Chen; Bo Li; Zhuhui Jiang; Xiaoqiong Zhen; Xiaoguang Sun; Xiangao Xia (Atmospheric Research, 2026)

Characterization of groundwater discharge in an area of dense salt crust formation in the high-salinity South Huobuxun Lake (NW China) using isotopic and hydrogeochemical analyses - Xinming Song; Fu Liao; Guangcai Wang; Nuan Yang; Xianglong Chen; Bo Li (Hydrogeology Journal, 2026)

Two new compounds from the roots of Paeonia lactiflora Pall. and their anti-inflammatory effects - Bo Fu; Jin-Ling Zhang; Jia-Tong Wu; Si-Yi Wang; Yi-Qiang Zhang; Juan Pan; Wei Guan; Zhi-Chao Hao; Hai-Xue Kuang; Qing-shan Chen; Li-Li Zhang; Bing-You Yang; et al. (Natural Product Research, 2026)

Principle analysis and device development of a novel technology for preventing lockset failure and cable bolt ejection - Housheng Jia; Zhiming Zhang; Yanxi Gao; Mengxiong Fu; Guoying Wang; Chao Li; Bo Peng; Wenyuan Jiang (Tunnelling and Underground Space Technology, 2026)

Identification of novel genes involved in pediatric congenital heart disease using trio-based whole genome sequencing - Bo Wang; Mo Li; Wei Zhou; Huiwen Chen; Ying Xiang; Guocheng Shi; Guoling You; Luan Chen; Yesheng Zhang; Xiaoqing Zhang; Yunqian Gao; Lulu Li; et al. (Science Bulletin, 2026)

Extreme load assessment and pitch control strategy for floating wind turbines considering the coupled effects of typhoon stage evolution and yaw error - Xiang Wang; Xu Liang; Peng You; Baoxuan Wang; Yue Chen; Fu Li; Bo Ye; Xianhui Zhu (Ocean Engineering, 2026)

Natural and anthropogenic controls on rare earth elements in groundwater: Indicative significance for distinguishing agricultural and urban-industrial impacts - Hang Meng; Guangcai Wang; Fu Liao; Hairu Mao; Bo Li; Fengxia Liu; Xianglong Chen; Hongyu Zhang; Zhiyuan Qiao (Journal of Hazardous Materials, 2026)

Flavor characterization of Chenxiang-type baijiu-Daoguang nianwu aged in wooden Jiuhai with different vintages integrating GC-E-nose, GC-IMS, GC-MS-O, ROAV and chemometrics approaches - Na Wang; Xiangyang Zhang; Li Xue; Zhen Zhang; Li Fu; Xuejiao Ren; Hui Zhang; Bo Zhang; Xiaoyu Jiang; Lili Zhang; Mei Wang (Food Research International, 2026)

Decoding the flavor formation mechanism of the functional microbial community in koji-mediated fish sauce - Jin-Xiu Xu; Xin Zhang; Bai-Feng Fu; Zhao-Rui Li; Min-Bo Li; Zhen-Yu Wang; Xian-Bing Xu; Shu-Zhen Cheng; Ming Du (Food Bioscience, 2026)

Multi-level metabolic engineering for efficient ergothioneine production in yeast using a Pleurotus ostreatus-derived pathway - Zhongjuan Di; Yanjun Huo; Yuejun Fu; Bo Li; Yingping Zhuang (Chemical Engineering Journal, 2026)

NAD+ depletion transdifferentiates the gastric stem cells to intestinal goblet cells in patient-derived gastric organoids - Bin Liu; Xiaoyang Zhang; Xia Xue; Fazhan Li; Feifei Ren; Ihtisham Bukhari; Baitong Hu; Xiangdong Sun; Bo Zhang; Yong Yu; Quan Zheng; Wanqing Wu; et al. (Chemical Engineering Journal, 2026)

Revisiting the Peripheral Nerve Injury and Regeneration - Zhen-Gang Liu; Yun-Long Zou; Min-Xin Zhang; Fan Yang; Peng-Fu Li; Bo-Yin Zhang (NeuroMolecular Medicine, 2026)

The Protective Role of Selenium Against Thyroid Injury in Pigs: Involvement of PINK1/Parkin-Mediated Mitophagy and Apoptosis Regulation - Xuehan Jiang; Yishan Yin; Yi Fang; Hongxue Yang; Hongyu Fu; Bo Li; Xiaoxiao Chen; Bendong Shi; Jingzeng Cai; Ziwei Zhang (Biological Trace Element Research, 2026)

Influence of fines content on shear strength and fabric evolution of unbound aggregate base: An experiment and simulation study - Bo Li; Zhengcao Du; Zhenzheng Liu; Jianbing Ma; Zhaoxiang Li; Weiguang Ma; Yunpeng Zhang; Maoyi Fu; Yongping Hu (Transportation Geotechnics, 2026)

Eocene topography differentiation between the western and eastern North China Craton: Insights from multi-method chronometry in the northern Taihangshan Mountains - Li-Xia Feng; Ping-Ping Li; Zeng-Zhen Wang; Rong Ren; Lin Wu; Bo Zheng; Bo Liu; Jian-Qing Ji; Bao-Fu Han (Tectonophysics, 2026)

Effect of perovskite A-site disorder on its activity in solid-state CO2 electrolysis - Shuo Liu; Lin-Bo Liu; Biao Ouyang; Yan Li; Qinglin Pan; Yifei Sun; Xian-Zhu Fu; Jing-Li Luo; Subiao Liu (Chemical Engineering Journal, 2026)

Electrochemical aptamer sensor based on nanocomposites composite material for rapid on-site detection of enrofloxacin in aquaculture - Bo Long; Qi Liu; Yizhuan Li; Qiongqiong Xing; Chuxiong Lan; Rui You; Liying Deng; Fangfang Qu; Meng An; Yingchun Fu; Shenghang Zhang; Dapeng Ye; et al. (Chemical Engineering Journal, 2026)

Integrating Cost-Sensitive Ensemble Learning and Geoscience Big Data for Uranium Prospectivity Mapping in the Husab Uranium Deposit, Namibia - Yuan Li; Chen Fu; Yingxu Song; Jiahui Zhang; Yu Li; Bo Liu; Yingcong Huang; Dajun Li (Natural Resources Research, 2026)

Research on application of modified low-carbon magnesium oxysulfate cement for grouting reinforcement in crushed limestone tunnels - Junfu Fu; Junru Zhang; Ziyan Fan; Bin Li; Huayun Li; Jimeng Feng; Bo Wang; Xiping Ma (Tunnelling and Underground Space Technology, 2026)

Impact of soil compaction and seasonal freeze-thaw cycles on the microstructural evolution and aggregate stability of Mollisol - Boxiang Zhang; Bo Liu; Shuang Li; Juan Fu; Yanfeng Jia; Haoming Fan; Chengjiu Guo; Fangli Su; Renming Ma (Soil and Tillage Research, 2026)

Catalysis-inspired d-band center engineering enables hydrogen-suppressed zinc anodes for long-life aqueous zinc-ion batteries - Chunhui Gao; Zhenjing Jiang; Jie Chen; Kaining Zhang; Huijun Yang; Ruwei Chen; Hang Yang; Qingjin Fu; Zheng Li; Nana Xu; Mengran Wang; Bo Hong; et al. (Science Bulletin, 2026)

High-resolution elastic full-waveform inversion using dual-channel CNN and Kolmogorov–Arnold network - Faxuan Wu; Yang Li; Zhenwu Fu; Bo Han; Yong Chen (Journal of Applied Geophysics, 2026)

Corrigendum to “CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction” [Chem. Eng. J. 523 (2025) 168486] - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2026)

Hydraulic retention time extension and multi-point reflux promote full-scale partial mainstream anaerobic ammonium oxidation (Anammox) at low temperatures - Yang-Guang Xia; Jun-Hong Zhou; Xiao-Li Yang; Wen-Bo Liang; Yu-Jia Fu (Chemical Engineering Journal, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Zedoarondiol inhibits monocyte adhesion and expression of VCAM and ICAM in endothelial cells induced by oxidative stress - Bei-li Xie; Yu-long Bie; Bo-ce Song; Ming-wang Liu; Lin Yang; Jiangang Liu; Da-Zhuo Shi; Fu-Hai Zhao (Natural Product Research, 2026)

Arsenic species in crayfish from the Yangtze River basin, China: Levels composition and health risk assessment - Xinjie Li; Bo Fu; Kai Lin; Jiayin Huang; Sisi Yu; Wenchao Zhu; Yuli Lin; Chiqun Shan; Mingqin Zhong; Shaoyou Lu (Aquaculture, 2026)

Occurrence, drivers, and risk assessment of non-antibiotic pharmaceuticals in urban sewer systems - Fan Meng; Shaojing Sun; Jialu Cheng; Ziyi Wang; Changshun Wang; Jinpan Jiang; Lu Lu; Jingchao Li; Yajie Tian; Lixin Ma; Bo Li; Xiaoyu Feng; et al. (Environmental Pollution, 2026)

Experimental and numerical investigation on seismic performance of seawater sea-sand coral aggregate concrete filled UHPC tubular columns - Chengdong Lu; Dingkuan He; Bo Shan; Peicheng Qin; Tianyu Li; Bin Huang; Xinlin Fu; Gang Liu (Engineering Structures, 2026)

Energy-saving and fire/water-resistant recyclable aerogel coatings for thermal-insulating polyurethane foam - Cong-Mei Lin; Xue-Lian Chen; Fu-Rong Zeng; Li-Xiao Hao; Yu-Shi Wen; Bing-Ru Zhang; Bo-Wen Liu; Lin Zhang; Hai-Bo Zhao (Chemical Engineering Journal, 2026)

Molecularly imprinted polymers-based magnetic CoFe oxides nanozyme for the removal of Staphylococcus aureus and label-free quantitative detection - Jing Liu; Ran Chen; Jing-Wen Chen; Shao-Bo Li; Yue-Jie Li; Yong-Fu Huang; Zhi-Bin Chen; Li Li (Chemical Engineering Journal, 2026)

Manganese cycle-mediated synchronous bacteria-algae/anammox coupled denitrification system under low-temperature conditions: Performance and mechanisms - Peng-fei Yu; Dian-lin Jiang; Ding Wang; Xing-guan Ma; Jun-Li; Li-yao Han; Ao Wang; Yu-bo Fu; Xing Jin (Bioresource Technology, 2026)

Enhancing oil-water separation via droplet coalescence regulated by particle self-rotation in swirling fields - Wei Zhao; Ao-song Wei; Shu Zhu; Tong Zhang; Peng-bo Fu; Jian-ping Li; Xue-jing Yang; Hua-lin Wang (Water Research, 2026)

Development of a potent protective felinized chimeric antibody C8A8 targeting feline and canine parvovirus - Yajie Sun; Chengqi Zhang; Jiajia Liu; Dingrui Guo; Shuangshuang Li; Liwen Xu; Bo Hu; Haifeng Zeng; Yawen Liu; Jianhai Fu; Zichuang Zhang; Wenyu Cao; et al. (Veterinary Microbiology, 2026)

Monoculm1 confers cold tolerance at the seedling stage in rice - Ruiqing Li; Chenfan Zheng; Binqiang Wang; Shang Dai; Yue Song; Huali Zhang; Zhiguo E; Bo Liu; Jiale Chen; Can Zhang; Haowei Fu; Ning Xu; et al. (Molecular Plant, 2026)

Quercetin alleviates Deoxynivalenol-induced myocardial fibrosis in chicken by regulating MCU-mediated mitochondrial calcium overload - Hong-yu Fu; Yi Fang; Jia Chen; Hongxue Yang; Xuehan Jiang; Yishan Yin; Bo Li; Xiaoxiao Chen; Jingzeng Cai; Ziwei Zhang (Journal of Hazardous Materials, 2026)

Sunlight-driven evolution of the aroma profile in fish sauce fermentation - Jin-Xiu Xu; Xin Zhang; Bai-Feng Fu; Zhao-Rui Li; Min-Bo Li; Zhen-Yu Wang; Xian-Bing Xu; Shu-Zhen Cheng; Ming Du (Food Bioscience, 2026)

Non-contact preservation of chilled chicken: extending shelf life and modulating microbial dynamics using solid spice essential oils and modified atmosphere packaging - Xue Li; Dongwen Fu; Shuai Hu; Jinqing Huang; Li Wang; Yao Zhang; Cailing Liu; Bo Dong; Guangxian Liu (Food Control, 2026)

Vanillin-derived bio-based Schiff base for simultaneously enhancing flame retardancy, crystallizability and UV-shielding of poly(L-lactic acid) - Mengmeng Wei; Leihua Jia; Dandan Fu; Zhenhua Shi; Masrina Mohd Nadzir; Junsheng Wang; Yipaerguli Yiminniyazi; Li Fan; Qiran Wang; Fude Liu; Bo Wang; Jinjun Yang (Chemical Engineering Journal, 2026)

Ectomycorrhizal exploration types shape soil enzyme activity, decomposition, and nitrogen dynamics in subalpine forests - Lixia Wang; Haoying Gao; Shuangjia Fu; Huichao Li; Lin Xu; Li Zhang; Han Li; Chengming You; Sining Liu; Hongwei Xu; Jiao Li; Bo Tan; et al. (Plant and Soil, 2026)

The persistent threat of Niphades castanea to China’s chestnut across three major river basins - Bin Mao; Yue Fu; Ya-Bo Liu; Hui-Ling Yang; Yun-Li Xiao (New Forests, 2026)

Corrigendum to “Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk” [Toxicology and Applied Pharmacology Volume 503, October 2025, 117465]. - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Aggregate size mediates the stability and temperature sensitivity of soil organic carbon in response to decadal biochar and straw amendments - Yalan Chen; Yakov Kuzyakov; Qiwen Ma; Zhangliu Du; Ke Sun; Keqing Xiao; Xinru Liang; Yang Li; Yunxian Zhang; Xianqiang Lai; Wei Fu; Bo Gao; et al. (Soil Biology and Biochemistry, 2025)

Phytochemical profiling of Bai traditional food: Eight previously undescribed meroterpenoids derivatives with cytotoxic potential from the flowers of Rhododendron pachypodum - Ying Wang; Jie Luan; Ji-Ai Wang; Xiu Chen; Fu-Cai Ren; Bing Chen; Jing Jia; Gao-Hong Zhang; Yong Li; Jiang-Bo He (Phytochemistry, 2025)

Optimal matrix identification of parabens, triclosan and triclocarban for biomonitoring: Comparative analysis in urine, whole blood, serum, and plasma - Weizhong Chen; Yuli Lin; Kai Lin; Xiaoru Wu; Chiqun Shan; Bo Fu; Yiran Chen; Junye Bian; Xinjie Li; Xulong Chen; Tao Chen; Guangyu Sun; et al. (Journal of Hazardous Materials, 2025)

Structural dynamics and multifunctionality of zero-dimensional Sb-based halides: Unveiling anomalous thermal quenching and pressure-driven luminescence control - Daxi Pan; Liangyi Gu; Bo Wang; Xiaoshuang Li; Jingrui Zhang; Jiahong Li; Ruijing Fu; Youchao Kong; Qingguang Zeng (Journal of Environmental Chemical Engineering, 2025)

GRACE-derived spatiotemporal changes of terrestrial water storage in the major plateaus of China - Dong Wang; Bo-Hui Tang; Yingyun Li; Wei Fu; Zhitao Fu; Zhen Zhang; Zhongxi Ge (Global and Planetary Change, 2025)

Soil and retaining wall responses induced by horizontal soil arching - Zhuofeng Li; Jiefei Fu; Shuangqin Li; Bo Yang; Peng Xia; Yunmin Chen (Computers and Geotechnics, 2025)

Ambient-dried polymer aerogel engineered via interparticle “stringing” towards ultrahigh robustness, flame retardancy and harsh-environment durability - Ting-Ting Li; Ting Wang; Chengxu Xu; Xue Gou; Xi-Ping Huang; Si-Yao Zhong; Zhi-Cheng Fu; Jinni Deng; Wenli An; Hai-Bo Zhao; Ming-Jun Chen (Chemical Engineering Journal, 2025)

Floc-granule microbial symbiosis drives DNRA in anammox bacteria via cross-feeding for complete autotrophic nitrogen removal - Yulong Yang; Wen-Bo Nie; Xin Tan; Lili Li; Chenhui Yu; Shibo Fu; Ke-Di Peng; Yi Luo; Xiao Ran; Zhihong Zheng; Jin Xu; Jun Li; et al. (Chemical Engineering Journal, 2025)

Pluvial flood warnings in a tidally influenced basin enhanced by rainfall–tide compound indicators: Taipei case study - Mei-Ying Lin; Wen-Yih Sun; Huei-Syuan Fu; Chih-Hsin Chang; Wei-Bo Chen; Chieh-Ju Wang; Hsuan-Wei Wang; Yi-Chiang Yu; Yen-Wei Li (Stochastic Environmental Research and Risk Assessment, 2025)

From heterogeneity to prognosis: understanding the complexity of tertiary lymphoid structures in tumors - Yingying Wang; Dongyan Zhang; Xueping Huang; Guohao Wu; Chuanbao Wang; Jun Li; Song Wang; Xinmiao Xian; Bo Fu; Keyi Li (Molecular Biology Reports, 2025)

Wavelength-dependent photobiomodulation attenuates synovial inflammation in fibroblast-like synoviocytes and a collagenase-induced osteoarthritis model - Tianxiang Fan; Peng Xia; Safayet Ahmed; Yuen H. Tsang; Zhi Yao; Deli Wang; Ziyu Chen; Lixiang Xue; Dongquan Shi; Bo Wang; Chi Fai Cheung; Marco Y.C. Pang; et al. (Journal of Photochemistry and Photobiology B: Biology, 2025)

Machine learning-guided anti-photoaging peptides from Chinese giant salamander skin: Efficient preparation and mechanistic insights - Yongjie Zhou; Huijuan Zhang; Chunyue Zhao; Zixin Fu; Yuting Wang; Sam K.C. Chang; Yan Zhang; Hui Hong; Yongkang Luo; Bo Li; Yuqing Tan (Food Chemistry, 2025)

CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2025)

The recovery mechanism of granular sludge fragmentation and re-granulation caused by long-term high-concentration organic matter erosion in the SAD process: performance, sludge evolution, and metagenomic sequencing - Peng-fei Yu; Ding Wang; Yu-bo Fu; Xing-guan Ma; Hao Zheng; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Xing Jin (Bioresource Technology, 2025)

Four new acylphloroglucinol glucoside derivatives from the leaves of Lysidice rhodostegia - Tian-Yuan Wu; Wei-Xuan Zheng; Xuan Zhou; Kai Zhao; Wei Wu; Li-Qin Zhan; Jin-Tao Fu; Qing Tang; Yu-Bo Zhang; Wen Li; Guo-Cai Wang (Natural Product Research, 2025)

The response of plant-derived lignin phenols accumulation to nutrient addition depends on soil depth in a subtropical plantation - Jin He; Dong Bu; Yuan-Huang Zeng; Shui-Bo Han; Wen-Qing Li; Fu-Sheng Chen; Ying-Ying Zong; Yu-Xin Huang; Yang Zhang; Xiang-Min Fang (Plant and Soil, 2025)

A chemometric approach for FTIR-Raman-LIBS tri-modal spectral fusion: Transformer-based accurate identification of recyclable polymers - Wenxia Xu; Zhuoqing Fu; Bo Tang; Jun Xu; Guodong Li (Analytica Chimica Acta, 2025)

Two new withanolides from Physalis minima L - Li-Jie Zhang; Mei-Lin Peng; Shi-Ying Xu; Fu-Rui Wang; Lin-Lin Yu; Qin-Feng Zhu; Shang-Gao Liao; Guo-Bo Xu (Natural Product Research, 2025)

Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Middle Campanian to Maastrichtian foraminifera and biomarkers: Seawater incursion events in the Songliao Basin, Northeast China - Ke-Ying Yue; Sha Li; Tian Jiang; Dang-Peng Xi; Bo-Wen Song; Yu Liang; Li-Xin Sun; Tian-Fu Zhang; Hai-Chun Zhang; Xiao-Qiao Wan; Bo Wang (Palaeoworld, 2025)

The influence of water flow disturbance form on the granulation of algae sludge: Granulation property, treatment effect and algae biological structure - Peng-fei Yu; Ao Wang; Hai-wen Sun; Ding Wang; Xing-guan Ma; Yu-jia Wang; Bo-mei Hu; Li-yao Han; Yu-bo Fu; Dian-lin Jiang; Shi-gang Tu (Journal of Water Process Engineering, 2025)

WB-assisted activation of periodate by Fe(III) for decontamination: Periodate concentration-dependent mechanistic shift - Yulu Xu; Yu Mei; Yanjun Li; Chenye Fu; Yuantai Li; Yuheng Zhong; Junxi Song; Gang Yang; Shihuai Deng; Xiaohui Lu; Jiali Peng; Bo Lai (Journal of Hazardous Materials, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

Polyacrylic acid promotes anti-passivation and electron-donation of boronized nanoscale zero-valent iron during groundwater remediation - Zelong Zheng; Lihang Ma; Xiaobin Liao; Ming-Lai Fu; Baoling Yuan; Xiao-yan Li; Yi-bo Hu (Chemical Engineering Journal, 2025)

Nitrilotriacetic acid-assisted activation of periodate by Fe(III) for organic pollutant degradation: the critical roles of high-valent iron species formation and coordination inhibition by phenolic contaminants - Xiaohui Lu; Yuantai Li; Shihuai Deng; Yanjun Li; Chenye Fu; Guochun Lv; Da Wang; Junxi Song; Hong Xiao; Jiali Peng; Bo Lai (Chemical Engineering Journal, 2025)

van der Waals heterojunction-based NO2 chemosensor via a synergistic halogen bond site - Wen Luo; Huan Liu; Zhen Zhu; Bo Wang; Wenxing Xu; Ximeng Luo; Chunhui Li; Yanyan Fu; Huizi Li; Huimin Cao; Wei Xu; Qingguo He; et al. (Chemical Engineering Journal, 2025)

Synthesis of expanded microcrystalline graphite/Mn0.4Zn0.6Fe2O4 composites for electromagnetic wave absorption - Mingzhe Liu; Bo Wang; Yujiang Wang; Binchuan Li; Daxue Fu; Yongfeng Chang; Jianshe Chen; Kuiren Liu; Qing Han; Xudong Lu; Cean Guo; Shicheng Wei (Chemical Engineering Journal, 2025)

Correction: Mapping the potential of biogas production for electricity generation from agricultural crop residues at the town scale in China - Zheng Yang; Hongqing Li; Bo Fu; Bing Xue; Vera Susanne Rotter (Environment, Development and Sustainability, 2025)

Vanadium-cobalt oxide nanoflower catalyst for efficient and stable overall water splitting in alkaline and seawater electrolytes - Yong-qi Tian; Song-lin Xu; Jia Li; Shuang-shuang Zhang; Bo-yao Zhang; Rong-da Zhao; Fu-fa Wu; De-peng Zhao (Next Research, 2025)

Perovskite-socketed FeCoNiCu quaternary alloy nanoparticles for efficient CO2 reduction in solid oxide electrolyzer - Shuo Liu; Lin-Bo Liu; Ming Yang; Yan Li; Qinglin Pan; Yifei Sun; Xian-Zhu Fu; Subiao Liu; Jing-Li Luo (Chemical Engineering Journal, 2025)

Bioinspired neural network-enabled metre-scale attached ultraductile cementitious nanosensors with temperature-immune - Hua Fu; Penggang Wang; Heping Zheng; Bo Pang; Zuquan Jin; Xiaoyun Song; Li Tian; Zhenxing Du; Bukhari Mohd Nadeem; Peng Zhang; Zhengkai Hu (Chemical Engineering Journal, 2025)

Dual-defect engineering strategy induced polarization loss in trimetallic MOFs/MXene-derived nanocomposites for broadening microwave absorption bandwidth - Yuanzhao Hou; Binchuan Li; Kuiren Liu; Jianshe Chen; Yongfeng Chang; Bo Wang; Shicheng Wei; Xiaocai He; Da Li; Chul B. Park; Daxue Fu; Qing Han (Chemical Engineering Journal, 2025)

Evolution of fire activity in arid Central Asia since ∼12.9 ka: Transitioning from natural to anthropogenic forces - Wensheng Zhang; Guoqiang Ding; Yong Zhang; Yuecong Li; Bing Li; Chao Lu; Bo Tan; Aijun Sun; Yang Fu; Chengbang An (CATENA, 2025)

Quorum-sensing Inhibitory Activity of Xanthones from Hypericum Curvisepalum N. Robson Against Chromobacterium Violaceum - Hong Zeng; Qiu-Ying He; Sheng-Qiang Yang; Xiao-Lian Wei; Jia-Zi Luo; Jing-Kai Zhou; Rong-Bing Fu; Li-Ping Teng; Zhong-Bo Zhou (Current Microbiology, 2025)

Multi-omics study reveals a light-dependent regulatory network of flavonoid biosynthesis in lettuce (Lactuca sativa L.) - Yuting Xiang; Shuxin Zheng; Hsihua Wang; Bang Chen; Rao Fu; Tao Huang; Li Zhang; Bo Song; Yuejian Li; Qichang Yang; Xiao Yang; Yang Zhang (Science China Life Sciences, 2025)

Mapping the potential of biogas production for electricity generation from agricultural crop residues at the town scale in China - Zheng Yang; Hongqing Li; Bo Fu; Bing Xue; Vera Susanne Rotter (Environment, Development and Sustainability, 2025)
The application of anaerobic digestion technology to crop residues plays a vital role in advancing sustainable agricultural development. In China, townships act as key regulators, essential for evaluating the energy potential of waste and implementing agricultural waste recycling policies. However, data at the township level often suffers from issues such as incomplete collection, inconsistent quality, and omissions. To address these challenges, we employed a multi-source data approach—including official statistics, field surveys, remote sensing imagery, and laboratory experiments—to ensure comprehensive and reliable data coverage. This study utilizes four distinct models: Biochemical Methane Potential, a simplified Anaerobic Digestion Model No. 1, Gradient Boosting, and Random Forest to calculate biogas production potential from crop residues. By integrating these models with Geographic Information Systems, we delineate the potential for electricity generation from biogas production at the township level throughout China. Despite variations in the input data across different models, the maximum output discrepancy is limited to 13.4% (i.e., the maximum relative deviation between each model’s output and the mean output for each crop), indicating minor differences. This finding underscores the flexibility in model selection based on the availability of data. Moreover, our analysis reveals that local biomass straw residue can fulfill around 11% of residential electricity demands. This research introduces an innovative and comprehensive methodology that integrates multiple predictive models with Geographic Information Systems (GIS) to assess the energy potential of crop residues for biogas production at the township scale, thereby providing a robust framework to inform energy policy development and management strategies.

Analysis of intrinsic effects of compound curing agents on small molecule metabolites and microbial communities in Xuanwei ham based on metabolomics and high-throughput sequencing - Zhijie Zheng; Wenxi Fu; Guiying Wang; Bo Li; Wen Xun; Nannan Zhou; Chunfang Yang; Ruwei Ren; Shuai Tang; Yanfei Du; Jiayan Tan; Dahai Gu; et al. (Meat Science, 2025)

Unveiling the mechanism of fermentation induced antioxidant activity enhancement in asparagus juice: Metabolomic and transcriptomic insights into the functional role of Lactiplantibacillus plantarum JGS 49 - Jinqing Huang; Li Wang; Xue Li; Yao Zhang; Bo Dong; Shuai Hu; Cailing Liu; Dongwen Fu; Lecheng Shen; Guangxian Liu (Food Bioscience, 2025)

pH-responsive drug-targeted delivery system: Dual-drug loading hollow mesoporous silica for synergistic therapy bacterial enteritis of Micropterus salmoides - Yuan-shuai Fu; Yue Lin; Wen-jun Zhong; Xing-yu Wang; Xi-ke Li; Yun-ao Li; Sheng-bo Ye; Wen-juan Li; Yong-heng Zhu (Chemical Engineering Journal, 2025)

Bioinspired structural laminates with superior ice-repellence and damage resistance for aviation applications - Mingdi Shi; You Pan; Haixiao Cao; Yongxin Guo; Xue Sun; Yuan Fu; Yihang Wu; Yufei Luo; Yangyu Lu; Zhenting Wu; Liang Jiang; Bo Li; et al. (Chemical Engineering Journal, 2025)

Forest conversion and root trenching reshape microbial functions regulating root litter decomposition and soil carbon dynamics - Lixia Wang; Shuangjia Fu; Haoying Gao; Huichao Li; Yang Liu; Lin Xu; Li Zhang; Han Li; Chengming You; Sining Liu; Hongwei Xu; Bo Tan; et al. (Applied Soil Ecology, 2025)

Chitosan Nano-Selenium Supplementation Improves Production Performance, Egg Quality, and Selenium Deposition in Aging Laying Hens - Gang Shu; Xin Yi; Lei Yang; Jingyi Chen; Kang Fu; Haohuan Li; Funeng Xu; Wei Zhang; Hualing Fu; Bo Jing; Felix Kwame Amevor; Yingjie Wang; et al. (Biological Trace Element Research, 2025)

Rigid polyelectrolyte multilayer membrane with ultrahigh permeance and excellent dye/salt separation performance - Na Zhang; Fanglu Fu; Wen Bo; Hussein Baqiah; Li Zhao; Wenbo Lu; Yadi Cai; Jiahui Tian; Tingting Yan; Saisai Li; Shuyun Zheng; Qiang Li (Journal of Environmental Chemical Engineering, 2025)

Inorganic arsenic in aquatic products in Shenzhen, China from 2018 to 2024: Levels, temporal variation and health risk assessment - Bo Fu; Kai Lin; Sisi Yu; Yiming Ge; Xinjie Li; Wenchao Zhu; Lei Tan; Rui Wang; Jixi Ou; Shaoyou Lu (Food and Chemical Toxicology, 2025)

Wide-bandgap perovskite solar cells with > 1.34 V Voc for all-perovskite tandems - Yunfei Li; Nannan Sun; Bo Feng; Wen Li; Zhengbo Cui; Wenxiao Zhang; Sheng Fu; Xiaodong Li; Junfeng Fang (Chemical Engineering Journal, 2025)

Deep eutectic solvents for ginsenoside extraction and inhibition of ginsenoside hydrolysis in Panax notoginseng leaves: methodology and mechanistic insights - Jia-Yue Liu; Shi-Yao Hua; Li-Juan Ma; Xin Tao; Wen-Yu Fu; Jian-Bo Wan (Chemical Engineering Journal, 2025)

The nickel hyperaccumulator Odontarrhena chalcidica (Brassicaceae) preferentially takes up zinc over nickel - Ya-Zhou Wang; Ke-Rui Geng; Bing-Lan Mo; Ting Liu; Ye-Tao Tang; Dian Wen; Fu-Rong Li; Xu Wang; Lei Li; Rui-Ying Du; Antony van der Ent; Teng-Hao-Bo Deng; et al. (Plant and Soil, 2025)

PRDX1 affects acrylamide-induced neural damage through the PTEN/AKT signaling pathway - Dong-Xue Fu; Ya-Ting Lei; Hai-Bo Guo; Ting Chen; Xiang-Ying Gao; Xiao-Li Wang; Xiang Huang; Ling-Ling Song; Sheng-Yuan Wang; Qin-Xue Dai (NeuroToxicology, 2025)

Conductive characterization of shale reservoir induced by pore fluids: A case study of longmaxi formation in Southern Sichuan region - Yanran Li; Bo Liu; Zhiming Hu; Changhong Cai; Qingxiu Zhang; Jingshu Guo; Shuti Zeng; Fu Li (Fuel, 2025)

Mechanochemical treatment boosted microwave-assisted sulfonation of softwood lignin for the fabrication of dye dispersant - Xu Fu; Ling-Ping Xiao; Bo-Wen Meng; Wen-Jie Li; Run-Cang Sun (Chemical Engineering Journal, 2025)

Thermoacoustoelasticity for Elastic Wave Propagation in Preheated and Prestressed Solid Rocks - Jian Yang; Li-Yun Fu; Tongcheng Han; Wubing Deng; Bo-Ye Fu (Rock Mechanics and Rock Engineering, 2025)

Development and evaluation of an electrical impedance tomography (EIT) sensor for real-time monitoring of hemolysis dynamics - Piao Peng; Yue Fu; Bo Che; Xuan Li; Lei Liu; Jing Sun; Teng Luo; Linhong Deng (Analytica Chimica Acta, 2025)

Chemical constituents of Pedicularis rex C. B. Clarke and their hepatoprotective activities - Yang Fei-Yu; Liu Huai-Qin; Fu-Rui Wang; Zhang Li-Jie; Liao Xing-Jiang; Guo-Bo Xu; Qin-Feng Zhu; Shang-Gao Liao (Natural Product Research, 2025)

Physiological and molecular evidence for phycobilisome degradation in maintaining carbon and nitrogen balance of cyanobacteria - Zhen Luo; Shuangqing Li; Muhammad Zain Ul Arifeen; Fei‑xue Fu; Huayang Gao; Taoran Sun; Lingmei Liu; Xumei Sun; Xinwei Wang; Hai-Bo Jiang (Marine Life Science & Technology, 2025)
Phycobilisomes (PBS), the primary light-harvesting complexes in cyanobacteria, are degraded under nitrogen starvation to provide nitrogen for cell growth. This study reveals that carbon supply is a critical prerequisite for PBS degradation under nitrogen deficiency in Synechococcus sp. PCC 7002. Even under nitrogen-deficient conditions, PBS degradation is inhibited in the absence of sufficient carbon. We demonstrate that both the nblAB -mediated PBS-degradation pathway and the ccmLMNK operon-mediated CO 2 -concentrating mechanism are essential for PBS degradation. Furthermore, our findings highlight the critical role of PBS degradation in cyanobacterial adaptation to high C/N conditions. Mutant strains (Mut- nblA and Mut- nblB) deficient in PBS degradation exhibited impaired adaptation to high C/N conditions, as evidenced by their inability to thrive in high NaHCO 3 (nitrogen-free) or CO 2 (low-nitrogen) environments. While these mutants displayed a greener phenotype under high C/N conditions compared to the wild type, they exhibited extensive cellular damage, and significant downregulation of photosynthesis-related genes. These results provide novel insights into the carbon-dependent regulation of PBS degradation and its essential role in cyanobacterial C/N balance, highlighting its significance for their adaptation to fluctuating environmental conditions.

Genome skimming for improved phylogenetics of Taiwanese phasmids (Insecta: Phasmatodea) - Bo-Cheng Wang; Ming-Luen Jeng; Jing-Fu Tsai; Li-Wei Wu (Molecular Phylogenetics and Evolution, 2025)

Hybrid crosslinking cellulose nanofibers-reinforced zwitterionic poly (ionic liquid) organohydrogel with high-stretchable, anti-freezing, anti-drying as strain sensor application - Dong Fu; Linhui Xing; Yang Xie; Peng Li; Fan Yang; Xin Sui; Jiaying Liu; Jialong Chi; Bo Huang; Jun Shen (Carbohydrate Polymers, 2025)

Correction to: Metanephric mesenchyme-derived Foxd1+ mesangial precursor cells alleviate mesangial proliferative glomerulonephritis - Meiling Jin; Zhong Yin; Kai Wei; Yuansheng Xie; Xueyuan Bai; Bo Fu; Zhe Feng; Qinggang Li; Xiangmei Chen (Journal of Molecular Medicine, 2025)

N-doped carbon nanotubes encapsulated Ni3ZnC0.7 nanoparticles catalyst for peroxymonosulfate activation: Heterojunction structure and N-doping enhance electron transfer capability - Qihao Sun; Huiyuan Deng; Na Zhao; Junjie You; Zhicheng Pan; Bo Xing; Yuling Ye; Bo Lai; Xinye Yang; Xinjie Wang; Yunhui Lu; Jian Li; et al. (Chemosphere, 2025)

Activation of persulfates on carbon nanotubes for water decontamination: Is the non-radical process consistently considered across different pH levels? - Jiali Peng; Lun Li; Shihuai Deng; Hongyu Zhou; Yanjun Li; Chenye Fu; Long Lin; Yue Yuan; Wei Wei; Guochun Lv; Gang Yang; Xiaohui Lu; et al. (Journal of Hazardous Materials, 2025)

Distinguishing the self-ignition and ignition temperatures of coal based on Semenov’s thermal explosion theory - Yang Liu; Zezheng Shi; Yongxiao Jia; Zhaoshuai Chen; Bo Yu; Kuangyu Li; Zhi Wang; Xinyu Wang; Yumin Chen; Peifang Fu; Huaichun Zhou (Fuel, 2025)

The effect of soil depth on stoichiometry was greater than that of elevation in Abies georgei var. Smithii forest in Southeastern Tibet, China - Si-jie Zhu; Jiang-rong Li; Bo Zhang; Fang-wei Fu; Liang-na Guo (Acta Oecologica, 2025)

A multitemporal remote sensing thick cloud removal network based on implicit reconstruction - Ke Zhang; Han Nie; Weitong Li; Jianxin Wang; Bo-Hui Tang; Leiguang Wang; Zhitao Fu (International Journal of Remote Sensing, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Anisotropic acoustoelastic effective-medium model for stress-dependent elastic moduli of fractured rocks - Bo-Ye Fu; Li-Yun Fu (International Journal of Rock Mechanics and Mining Sciences, 2025)

Wastewater-based monitoring of antipyretics use during COVID-19 outbreak in China and its associated ecological risks - Chao Yu; Jianhe Zhang; Xiaofang Fu; Bo Zhou; Jianwen Huang; Jun Qin; Xiqing Li (Environmental Research, 2025)

A systematic review on heavy metals in indoor air: Occurrence, spatial variation, and health risk - Ni Liang; Zekun Li; Jie Sun; Nan Fu; Guoliang Zhong; Xianbiao Lin; Kang Mao; Peng Zhang; Zhaofeng Chang; Dong Yang; Wei Du; Guofeng Shen; et al. (Building and Environment, 2025)

Hydrochemical characteristics and evolution of geothermal waters in western Yunnan, China based on self-organizing map and hydrogeochemical simulation - Bo Li; Guangcai Wang; Fei Liu; Zheming Shi; Qingmin Kong; Shouchuan Zhang; Xin Yan; Fu Liao; Liang Guo; Chenglong Liu (Applied Geochemistry, 2025)

An enhancer–promoter-transcription factor module orchestrates plant immune homeostasis by constraining camalexin biosynthesis - Ying Zhang; Meng Tang; Yi Zhang; Qinglin Cheng; Lijiang Liu; Wei Chen; Jiatao Xie; Jiasen Cheng; Yanping Fu; Bo Li; Daohong Jiang; Xiao Yu (Molecular Plant, 2025)

Microbiome changes and characteristics under nutrient injection for enhanced oil production at Daqing oilfield - Zi-Yue Fu; Wen-Tao Chen; Gui-Na Qi; Zhao-wei Hou; Yi-Fan Liu; Li-Bin Shou; Lei Zhou; Shi-Zhong Yang; Xiao-Lin Wu; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2025)

Regularization by double complementary priors for full waveform inversion - Hongyu Qi; Zhenwu Fu; Yang Li; Bo Han; Longsuo Li (Computers & Geosciences, 2025)

Development of “environmentally friendly” super Escherichia coli strains that can completely biodegrade toluene - Yu Wang; Cen Qian; Yong-Dong Deng; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Yuan-Zhang Sun; Hong-Juan Han; Wen-Hui Zhang; Hao Zhang; et al. (Chemical Engineering Journal, 2025)

A domain-decomposition-based parallel approach for 3D geological modeling using radial basis functions interpolation on GPUs - Hong Li; Huizhu Ni; Jinming Fu; Bo Wan; Deping Chu; Fang Fang; Run Wang; Guoxi Ma; Xin Zhou (Earth Science Informatics, 2025)

Joint Retrieval of PM2.5 Concentration and Aerosol Optical Depth over China Using Multi-Task Learning on FY-4A AGRI - Bo Li; Disong Fu; Ling Yang; Xuehua Fan; Dazhi Yang; Hongrong Shi; Xiang’ao Xia (Advances in Atmospheric Sciences, 2025)

Life cycle assessment of hydrogenotrophic denitrification in membrane aerated biofilm reactors for sustainable wastewater treatment - Rui Li; Ming-yi Lu; Rong-bo Guo; Haoran Duan; Bing-jie Ni; Shan-fei Fu (Water Research, 2024)

Effects of microplastics separate exposure and co-exposure to 17β-estradiol on the productive performance of juvenile female Chinese mitten crab (Eriocheir sinensis) - Yang Fu; Jian Zhang; Yilong Cui; Bo Li; Siming Huo; Jiayu Du; Yanfei Li (Science of The Total Environment, 2024)

Introduction to special issue LED 2023 - Naomi Porat; Frank Preusser; Bo Li; Christophe Falgueres; Fu Xiao; Georgina King; Jakob Wallinga; Julie Durcan (Quaternary Geochronology, 2024)

An improved convolutional architecture for quantitative characterization of pore networks in fine-grained rocks using FIB-SEM - Bo Liu; Qamar Yasin; Mengdi Sun; Atif Ismail; David A. Wood; Xin Tian; Baiquan Yan; Li Fu (International Journal of Coal Geology, 2024)

Real-time monitoring of activated sludge flocs via enhanced mask region-based Convolutional Neural networks - Tie-Fu Xu; Cai-Ling He; Guo-Tao Wang; Bo-Wen Li; Yu Tao (Environmental Research, 2024)

Decoding PTEN: from biological functions to signaling pathways in tumors - Xueping Huang; Dongyan Zhang; Di Zhang; Jianran Guo; Guohao Gu; Yingying Wang; Guohao Wu; Chuanbao Wang; Bo Fu; Keyi Li (Molecular Biology Reports, 2024)

Correlations and stoichiometric characteristics of C, N, and P contents in Juniperus saltuaria plants, litter, and soil in the Sygera Mountains, southeastern Xizang, China - Liangna Guo; Jiangrong Li; Fangwei Fu; Bo Zhang; Sijie Zhu; Yuzhuo Liu; Jieting Li; Ganggang Chen; Yibo Zhang (Journal of Mountain Science, 2024)

Diversity of biological activities of crude venom extracted from five species of South China Sea anemones - Panmin He; Ming Li; Jinxing Fu; Yanling Liao; Bo Yi; Bingmiao Gao (Frontiers in Marine Science, 2024)
Developing novel, efficient, and safe peptide drugs from sea anemones has aroused great interest in countries around the world today. Sea anemones contain complex protein and peptide toxins, which determine the diversity of their biological activities. In this study, a variety of activities were assessed for crude venom extracted from five species of South China Sea anemones, including hemolytic, enzyme inhibition, anticancer, insecticidal, analgesic and lethal activities. The most toxic sea anemone was found to be Heteractis magnifica , which has high lethal activity in mice with an LD 50 of 11.0 mg/kg. The crude venom of H. magnifica also exhibited a range of the most potent activities, including hemolytic, trypsin inhibitory, cytotoxic activity against U251 and A549 cells, insecticidal and analgesic activities. In addition, the crude venom of Stichodactyla haddoni was the most effective inhibitor of pepsin, and the crude venom of Heteractis crispa was extremely strong toxicity to HepG2 cells. These findings are of great significance for exploring the potential and application of South China Sea anemone resources, and are expected to provide new directions and possibilities for the development of novel anticancer drugs, analgesics and biopesticides.

Rapid and extensive SARS-CoV-2 Omicron variant infection wave revealed by wastewater surveillance in Shenzhen following the lifting of a strict COVID-19 strategy - Yinghui Li; Chen Du; Ziquan Lv; Fuxiang Wang; Liping Zhou; Yuejing Peng; Wending Li; Yulin Fu; Jiangteng Song; Chunyan Jia; Xin Zhang; Mujun Liu; et al. (Science of The Total Environment, 2024)

TBiSeg: A transformer-based network with bi-level routing attention for inland waterway segmentation - Chuanmao Fu; Meng Li; Bo Zhang; Hongbo Wang (Ocean Engineering, 2024)

Influences of released humic acids during thermal hydrolysis on sludge anaerobic digestion: New insights from the molecular weight of humic acids - Yaya Sun; Hongbo Liu; Jiaxin Wen; Hang Xiao; Mingze Shi; Xinlei Lu; Kai Shen; Xuedong Zhang; Bo Fu; Minhua Cui; Yajie Li; Salma Tabassum; et al. (Journal of Environmental Management, 2024)

Blood mercury mediates the associations between fish consumption and serum uric acid levels among Chinese adults: A nationally representative study - Changzi Wu; Bing Wu; Yingli Qu; Hui Fu; Yue Chen; Yifu Lu; Saisai Ji; Liang Ding; Zheng Li; Qi Sun; Miao Zhang; Xu Zhang; et al. (Environmental Research, 2024)

The toxic effects and mechanisms of maternal exposure to Bisphenol F during gestation and lactation on lungs in female offspring mice - Jiayu Du; Siming Huo; Bo Li; Xuliang Zhang; Jian Zhang; Yang Fu; Bing Shao; Yanfei Li; Miao Song (Environmental Pollution, 2024)

Valence electronic engineering of hollow-nanocube-structured CoFeNi-layered double hydroxides for highly efficient oxygen evolution - Lu Liu; Lingxing Zan; Yunchuan Tu; Hongling Zhang; Dan Zhu; Zhe Li; Jiawen Zheng; Zhuangzhuang Zhang; Yu Sun; Qiang Weng; Jian Li; Qingbo Wei; et al. (Chemical Engineering Journal, 2024)

Aflatoxin B1 as a complicit in intestinal damage caused by Eimeria ovinoidalis in lambs: Novel insights to reveal parasite-gut battle - Pan Chen; Wen-li Ding; Bo-wen Xu; Mujeeb Ur Rehman; Kai-li Liu; Yan-feng He; Sen-yang Li; Fu-chun Jian; Shu-cheng(淑成) Huang(黄) (Science of The Total Environment, 2024)

Experimental study on the elastic response characteristics of a rotating body under an oblique water impact load - Shao-Bo Li; Fu-Ren Ming; Tong-Shuai Peng; Yu-Tong Sui (Ocean Engineering, 2024)

Bayesian inversion of HFC-134a emissions in southern China from a new AGAGE site: Results from an observing system simulation experiment - Juan Li; Jianxiong Sheng; Lei Zhu; Bo Yao; Jing Wu; Dongchuan Pu; Lei Shu; Song Liu; Xicheng Li; Yuyang Chen; Xiaoxing Zuo; Yali Li; et al. (Atmospheric Environment, 2024)

Characteristics and ozone formation potentials of volatile organic compounds in a heavy industrial urban agglomeration of Northeast China - Yue Zhang; Bo You; Yijing Shang; Qiuyang Bao; Yanli Zhang; Xiaobing Pang; Li Guo; Jing Fu; Weiwei Chen (Air Quality, Atmosphere & Health, 2024)

Ancestral sequence reconstruction of the prokaryotic three-domain laccases for efficiently degrading polyethylene - Bo Zeng; Yishan Fu; Jiacai Ye; Penghui Yang; Shixiu Cui; Wenxuan Qiu; Yangyang Li; Taoxu Wu; Haiyun Zhang; Yachan Wang; Guocheng Du; Song Liu (Journal of Hazardous Materials, 2024)

Regulating the broadband near-infrared emission of Eu2+-doped Ca3Sc2Si3O12 phosphors through constructing defect for diversified applications - Chao Jiang; Quan Liu; Kaiyang Li; Yubo Feng; Yingkai Fu; Yue Li; Yicheng Zhang; Xu Qian; Bo Wei; Peng Du (Chemical Engineering Journal, 2024)

New approach for raw biogas: Production of single cell protein by sulfide-tolerant methane-oxidizing bacteria consortia - Hai-Ming Huang; Zhi-Xin Xue; Yu-Feng Jiang; Rui Li; Rong-Bo Guo; Xiao-Lei Fan; Shan-Fei Fu (Chemical Engineering Journal, 2024)

Corrigendum to “2′-O-galloylhyperin attenuates LPS-induced acute lung injury via upregulation antioxidation and inhibition of inflammatory responses in vivo” [Chem. Biol. Interact. 304 (1 May 2019) 20–27] - Sun-Dong Zhang; Peng Wang; Jing Zhang; Wei Wang; Li-Ping Yao; Cheng-Bo Gu; Thomas Efferth; Yu-Jie Fu (Chemico-Biological Interactions, 2024)

Coupling coordination analysis and obstacle factors of water-energy-environment-economy in the Yellow River Basin - Bo Pang; Xiaoxing Li; Yao Fu (Journal of Cleaner Production, 2024)

Impact of thermal ultrasound on enzyme inactivation and flavor improvement of sea cucumber hydrolysates - Yi-chao Cheng; Dan-li Jin; Wen-tao Yu; Bo-yang Tan; Jing-jing Fu; Yue-wen Chen (Food Chemistry, 2024)

Shear-induced permeability evolution of natural fractures in granite: Implications for stimulation of EGS reservoirs - Xuefeng Li; Fengshou Zhang; Nailing Xiu; Dingwei Weng; Bo Cai; Haifeng Fu (Engineering Geology, 2024)

Regulatory mechanisms of biochar alleviating ammonia inhibition to methanogenesis during long-term operation of anaerobic membrane bioreactor treating swine wastewater - Bo Zhang; Gaojun Wang; Xiang Zhang; Peng Fu; Lu Chen; Yizhi Chen; Qian Li; Rong Chen (Chemical Engineering Journal, 2024)

Molecular mechanism of a coastal cyanobacterium Synechococcus sp. PCC 7002 adapting to changing phosphate concentrations - Qiao-Wei Sun; Yu Gao; Jordan Wang; Fei-xue Fu; Cheng-Wen Yong; Shuang-Qing Li; Hai-Long Huang; Wei-Zhong Chen; Xin-Wei Wang; Hai-Bo Jiang (Marine Life Science & Technology, 2024)
Phosphorus concentration on the surface of seawater varies greatly with different environments, especially in coastal. The molecular mechanism by which cyanobacteria adapt to fluctuating phosphorus bioavailability is still unclear. In this study, transcriptomes and gene knockouts were used to investigate the adaptive molecular mechanism of a model coastal cyanobacterium Synechococcus sp. PCC 7002 during periods of phosphorus starvation and phosphorus recovery (adding sufficient phosphorus after phosphorus starvation). The findings indicated that phosphorus deficiency affected the photosynthesis, ribosome synthesis, and bacterial motility pathways, which recommenced after phosphorus was resupplied. Even more, most of the metabolic pathways of cyanobacteria were enhanced after phosphorus recovery compared to the control which was kept in continuous phosphorus replete conditions. Based on transcriptome, 54 genes potentially related to phosphorus-deficiency adaptation were selected and knocked out individually or in combination. It was found that five mutants showed weak growth phenotype under phosphorus deficiency, indicating the importance of the genes ( A0076 , A0549-50 , A1094 , A1320 , A1895 ) in the adaptation of phosphorus deficiency. Three mutants were found to grow better than the wild type under phosphorus deficiency, suggesting that the products of these genes ( A0079 , A0340 , A2284–86 ) might influence the adaptation to phosphorus deficiency. Bioinformatics analysis revealed that cyanobacteria exposed to highly fluctuating phosphorus concentrations have more sophisticated phosphorus acquisition strategies. These results elucidated that Synechococcus sp. PCC 7002 have variable phosphorus response mechanisms to adapt to fluctuating phosphorus concentration, providing a novel perspective of how cyanobacteria may respond to the complex and dynamic environments.

Correction to: Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao‑Bo Li; Yan‑Xun Han; Zi‑Yue Fu; Yu‑Chen Zhang; Min Fan; Shu‑Jia Sang; Xi‑Xi Chen; Bing‑Yu Liang; Yu‑Chen Liu; Peng‑Cheng Lu; Hua‑Wei Li; Hai‑Feng Pan; et al. (Environmental Science and Pollution Research, 2024)

Study on vibration effects of high-speed train operation on viaduct and subgrade-viaduct transition sections in loess area - Jin Chen; Xiaopeng Suo; Yixuan Li; Zhenjia Xu; Zhiren Hu; Yuewen Ma; Haonan Li; Bo Fu (Soil Dynamics and Earthquake Engineering, 2024)

Modelling the dynamic gas/particle partitioning process of semi-volatile organic compounds emitted from point sources: Quantitative analysis and impact assessment - Fu-Jie Zhu; Li-Fu Wang; Long-Ze Qu; Wan-Li Ma; Geng-Bo Ren; Ben-Hang Li; Xiao-Dong Ma (Science of The Total Environment, 2024)

Tomato NAC transcription factor NOR-like1 positively regulates tomato fruit softening - Zhen-Zhen Peng; Hong-Li Li; Gang-Shuai Liu; Xiao Su; Xiaodan Zhao; Donald Grierson; Lan-Ting Xiang; Jian-Lin He; Gui-Qin Qu; Hong-Liang Zhu; Ben-Zhong Zhu; Yun-Bo Luo; et al. (Postharvest Biology and Technology, 2024)

Nanobubbles improve peroxymonosulfate-based advanced oxidation: High efficiency, low toxicity/cost, and novel collaborative mechanism - Jun Bo Zhang; Jia Jie Zou; Chaomeng Dai; Jiajun Hu; Xueji You; Min-tian Gao; Jixiang Li; Rongbing Fu; Yalei Zhang; Kah Hon Leong; Xing Song Xu (Journal of Hazardous Materials, 2024)

The complete degradation of 1,2-dichloroethane in Escherichia coli by metabolic engineering - Yong-Dong Deng; Wen-Hui Zhang; Zhi-Hao Zuo; Hao Zhang; Jing Xu; Jian-Jie Gao; Bo Wang; Zhen-Jun Li; Xiao-Yan Fu; Li-Juan Wang; Yu Wang; Yong-Sheng Tian; et al. (Journal of Hazardous Materials, 2024)

Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao-Bo Li; Yan-Xun Han; Zi-Yue Fu; Yu-Chen Zhang; Min Fan; Shu-Jia Sang; Xi-Xi Chen; Bing-Yu Liang; Yu-Chen Liu; Peng-Cheng Lu; Hua-Wei Li; Hai-Feng Pan; et al. (Environmental Science and Pollution Research, 2024)
Air pollution can cause disease and has become a major global environmental problem. It is currently believed that air pollution may be related to the progression of SSNHL. As a rapidly developing city in recent years, Hefei has serious air pollution. In order to explore the correlation between meteorological variables and SSNHL admissions, we conducted this study. This study investigated the short-term associations between SSNHL patients admitted to the hospital and Hefei climatic variables. The daily data on SSNHL-related hospital admissions and meteorological variables containing mean temperature (T-mean; °C), diurnal temperature range (DTR; °C), atmospheric pressure (AP; Hp), and relative humidity (RH; %), from 2014 to 2021 (2558 days), were collected. A time-series analysis integrating distributed lag non-linear models and generalized linear models was used. PubMed, Embase, Cochrane Library, and Web of Science databases were searched. Literature published up to August 2023 was reviewed to explore the potential impact mechanisms of meteorological factors on SSNHL. The mechanisms were determined in detail, focusing on wind speed, air pressure, temperature, humidity, and air pollutants. Using a median of 50.00% as a baseline, the effect of exceedingly low T-mean in the single-day hysteresis effect model began at a lag of 8 days (RR = 1.032, 95% CI: 1.001 ~ 1.064). High DTR affected the admission rate for SSNHL on lag 0 day. The significance of the effect was the greatest on that day (RR = 1.054, 95% CI: 1.007 ~ 1.104) and then gradually decreased. High and exceedingly high RH affected the admission rate SSNHL on lag 0 day, and these effects lasted for 8 and 7 days, respectively. There were significant associations between all grades of AP and SSNHL. This is the first study to assess the effect of meteorological variables on SSNHL-related admissions in China using a time-series approach. Long-term exposures to high DTR, RH values, low T-mean values, and all AP grades enhance the incidence of SSNHL in residents. Limiting exposure to extremes of ambient temperature and humidity may reduce the number of SSNHL-related hospital visits in the region. It is advisable to maintain a suitable living environment temperature and avoid extreme temperature fluctuations and high humidity. During periods of high air pollution, it is recommended to stay indoors and refrain from outdoor exercise.

Chronic enhanced nitrogen deposition and elevated precipitation jointly benefit soil microbial community in a temperate forest - An Yang; Bo Song; Weixin Zhang; Tianning Zhang; Xiaowei Li; Hongtao Wang; Dong Zhu; Jie Zhao; Shenglei Fu (Soil Biology and Biochemistry, 2024)

Seasonal characterization of chemical and optical properties of water-soluble organic aerosol in Beijing - Bo You; Zhiqiang Zhang; Aodong Du; Yan Li; Jiaxing Sun; Zhijie Li; Chun Chen; Wei Zhou; Weiqi Xu; Lu Lei; Pingqing Fu; Shengjie Hou; et al. (Science of The Total Environment, 2024)

Turbulent transports in the flow around a rectangular cylinder with different aspect ratios - Jiang-hua Li; Bo-fu Wang; Xiang Qiu; Quan Zhou; Shi-xiao Fu; Yu-lu Liu (Ocean Engineering, 2024)

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

Sulphur evolution in acidic and alkaline geothermal water related to magma in the Rehai geothermal field in the southeastern Tibet Plateau based on stable hydrogen, oxygen, sulphur isotopes - Bo Li; Qingmin Kong; Fu Liao; Guangcai Wang; Fei Liu; Liang Guo; Chenglong Liu; Zheming Shi (Geothermics, 2024)

Probing into the radiative mechanisms and drivers influencing urban heat-cold islands and urban pollution islands during heavy-haze events in a cold megacity of Northeast China - Stephen Dauda Yabo; Lu Lu; Lixin Ma; Bo Li; Donglei Fu; Fan Meng; Jinpan Jiang; Xie Shengjin; Wei Zhang; Hong Qi (Atmospheric Research, 2024)

Green manure substitution for potassium fertilizer promotes agro-ecosystem multifunctionality via triggering interactions among soil, plant and rhizosphere microbiome - Qing Zeng; Mei Yin; Li-Bo Fu; Brajesh K. Singh; Si-Yi Liu; Hua Chen; An-Hui Ge; Li-Li Han; Li-Mei Zhang (Plant and Soil, 2024)

Long-chain acyl-CoA synthetase 4-mediated mitochondrial fatty acid metabolism and dendritic cell antigen presentation - Yan Li; Wenlong Fu; JinYing Xiang; Yinying Ren; Yuehan Li; Mi Zhou; Jinyue Yu; Zhengxiu Luo; Enmei Liu; Zhou Fu; Bo Liu; Fengxia Ding (Inflammation Research, 2024)

Proteomics Sequencing Reveals the Role of TGF-β Signaling Pathway in the Peripheral Blood of Offspring Rats Exposed to Fluoride - Fang-fang Yu; Shui-yuan Yu; Lei-zhen Duan; Shuo Yang; Xiang-bo Hou; Yu-hui Du; Ming-hui Gao; Juan Zuo; Lei Sun; Xiao-li Fu; Zhi-yuan Li; Hui Huang; et al. (Biological Trace Element Research, 2024)

CO2 sequestration in microbial electrolytic cell-anaerobic digestion system combined with mineral carbonation for sludge hydrolysate treatment - Wanying He; He Liu; Bo Fu; Chongjun Chen; Chao Zhang; Jing Li (Waste Management, 2024)

The hepatotoxicity of hexafluoropropylene oxide trimer acid caused by apoptosis via endoplasmic reticulum-mitochondrial crosstalk - Jiayu Du; Xuliang Zhang; Bo Li; Siming Huo; Jian Zhang; Yang Fu; Miao Song; Bing Shao; Yanfei Li (Science of The Total Environment, 2024)

Screening of toluene absorbents based on molecular simulation and experimental investigation on novel compound solvents - Li Wang; Kefan Chao; Zekai Jin; Muhua Chen; Xinbao Zhu; Gang Zhang; Bo Fu (Process Safety and Environmental Protection, 2024)

Crystal mush rejuvenation in the formation of Triassic dacites in Mengku, SE Tibetan Plateau - Feng Cong; Fu-Yuan Wu; Wen-Chang Li; Zai-Bo Sun; Xiao-Chi Liu; De-Feng He; Wei-Qiang Ji; Fang-Yang Hu; Shao-Hua Zhang; Xiao-Ming Huang (Journal of Asian Earth Sciences, 2024)

A review of combined fouling on high-pressure membranes in municipal wastewater reuse: Behaviors, mechanisms, and pretreatment mitigation strategies - Xiao-Yang Liu; Yu-Bo Chen; Jie Fu; Xianzheng Zhu; Long-Yi Lv; Li Sun; Guang-Ming Zhang; Zhi-Jun Ren (Chemical Engineering Journal, 2024)

Concentrated fireworks display-induced changes in aerosol vertical characteristics and atmospheric pollutant emissions - Lingjian Duanmu; Weiwei Chen; Li Guo; Jing Fu; Bo You; Hongwu Yang; Tianshu Zhang (Atmospheric Environment, 2024)

Comprehensive analysis of MAPK gene family in upland cotton (Gossypium hirsutum) and functional characterization of GhMPK31 in regulating defense response to insect infestation - Fuqiu Wang; Sijia Liang; Guanying Wang; Qiongqiong Wang; Zhongping Xu; Bo Li; Chunyang Fu; Yibo Fan; Tianyu Hu; Muna Alariqi; Amjad Hussain; Jinglin Cao; et al. (Plant Cell Reports, 2024)
Key message The transcriptomic, phenotypic and metabolomic analysis of transgenic plants overexpressing GhMPK31 in upland cotton revealed the regulation of H 2 O 2 burst and the synthesis of defensive metabolites by GhMPK31 . Abstract Mitogen-activated protein kinases (MAPKs) are a crucial class of protein kinases, which play an essential role in various biological processes in plants. Upland cotton ( G. hirsutum ) is the most widely cultivated cotton species with high economic value. To gain a better understanding of the role of the MAPK gene family, we conducted a comprehensive analysis of the MAPK gene family in cotton. In this study, a total of 55 GhMPK genes were identified from the whole genome of G. hirsutum . Through an investigation of the expression patterns under diverse stress conditions, we discovered that the majority of GhMPK family members demonstrated robust responses to abiotic stress, pathogen stress and pest stress. Furthermore, the overexpression of GhMPK31 in cotton leaves led to a hypersensitive response (HR)-like cell death phenotype and impaired the defense capability of cotton against herbivorous insects. Transcriptome and metabolomics data analysis showed that overexpression of GhMPK31 enhanced the expression of H 2 O 2 -related genes and reduced the accumulation of defensive related metabolites. The direct evidence of GhMPK31 interacting with GhRBOHB (H 2 O 2 -generating protein) were found by Y2H, BiFC, and LCI. Therefore, we propose that the increase of H 2 O 2 content caused by overexpression of GhMPK31 resulted in HR-like cell death in cotton leaves while reducing the accumulation of defensive metabolites, ultimately leading to a decrease in the defense ability of cotton against herbivorous insects. This study provides valuable insights into the function of MAPK genes in plant resistance to herbivorous insects.

Contrasting range changes of Bergenia (Saxifragaceae) species under future climate change in the Himalaya and Hengduan Mountains Region - Li Qiu; Qing-Li Fu; Hans Jacquemyn; Kevin S. Burgess; Jia-Jing Cheng; Zhi-Qiong Mo; Xiao-Dong Tang; Bo-Yun Yang; Shao-Lin Tan (Theoretical and Applied Climatology, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Curcumin inhibits the development of colorectal cancer via regulating the USP4/LAMP3 pathway - Hai Wei; Xianzhe Li; Fu Liu; Yuan Li; Bin Luo; Xin Huang; Hang Chen; Bo Wen; Pei Ma (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Knockdown of SIK3 in the CA1 Region can Reduce Seizure Susceptibility in Mice by Inhibiting Decreases in GABAAR α1 Expression - Zhen-Fu Jiang; Li-Na Xuan; Xiao-Wan Sun; Shao-Bo Liu; Jian Yin (Molecular Neurobiology, 2024)

Diisoprenyl-cyclohexene-type meroterpenoids from a mangrove endophytic fungus Aspergillus sp. GXNU-Y65 and their anti-nonalcoholic steatohepatitis activity in AML12 cells - Feng Qin; Li Luo; Yu-Chen Liu; Xiang-Long Bo; Fu-Rong Wu; Fan-Fan Wang; Mei-Jing Tan; You-Quan Wei; Xiao-Bing Dou; Cai Yi Wang; Xi-Shan Huang; Heng-Shan Wang (Phytochemistry, 2024)

Comparing the mechanisms of syntrophic volatile fatty acids oxidation and methanogenesis recovery from ammonia stress in regular and biochar-assisted anaerobic digestion: Different roads lead to the same goal - Gaojun Wang; Peng Fu; Yan Su; Bo Zhang; Mengyuan Zhang; Qian Li; Jianfeng Zhang; Yu-You Li; Rong Chen (Journal of Environmental Management, 2024)

Acoustoelastic DZ-MT model for stress-dependent elastic moduli of fractured rocks - Bo-Ye Fu; Li-Yun Fu (International Journal of Rock Mechanics and Mining Sciences, 2024)

Biogas upgrading by biotrickling filter: Effects of temperature and packing materials - Jie-Hua Huang; Xiao-Lei Fan; Rui Li; Meng-Ting Sun; Hua Zou; Yi-Feng Zhang; Rong-Bo Guo; Shan-Fei Fu (Chemical Engineering Journal, 2024)

Eco-friendly and stable triclosan removal from groundwater using peroxyacetic acid activated with biochar produced from saccharification residues - Wang Kai Tong; Chaomeng Dai; Chenyan Jia; Jiajun Hu; Min-tian Gao; Jixiang Li; Jun Bo Zhang; Han Tang; Yucang Liang; Wei Teng; Zhi Li; Shuguang Liu; et al. (Chemical Engineering Journal, 2024)

Rare earth element behaviors of groundwater in overlying aquifers under the influence of coal mining in northern Ordos Basin, China - Fengxia Liu; Guangcai Wang; Bo Li; Chenyu Wang; Shen Qu; Fu Liao (Environmental Science and Pollution Research, 2024)

Differences in soil microbial community structure and assembly processes under warming and cooling conditions in an alpine forest ecosystem - Fangwei Fu; Yueyao Li; Bo Zhang; Sijie Zhu; Liangna Guo; Jieting Li; Yibo Zhang; Jiangrong Li (Science of The Total Environment, 2024)

Self-assembled Fe3O4-NH2 @g-C3N4 composite for magnetic solid-phase extraction of benzophenones in sea water and lake water coupled with LC-MS/MS determination - Man-Man Wang; Zi-Ling Li; Han Wu; Ke-Yan Chen; Fan Guo; Gui-Fu Zuo; Yu He; Xue-Bo Yin (Journal of Hazardous Materials, 2024)

Identification and analysis of microplastics in human lower limb joints - Zhuo Li; Yifan Zheng; Zulipikaer Maimaiti; Jun Fu; Fan Yang; Zhi-Yuan Li; Yanli Shi; Li-Bo Hao; Ji-Ying Chen; Chi Xu (Journal of Hazardous Materials, 2024)

Overlooked encounter process that affects physical behaviors of stabilized nanoscale zero-valent iron during in situ groundwater remediation - Yujie Xie; Miaoyue Zhang; Lihang Ma; Ting Du; Dan Zhou; Ming-Lai Fu; Baoling Yuan; Xiao-yan Li; Yi-bo Hu (Journal of Hazardous Materials, 2024)

Mechanistic insights into synergistic facilitation of copper/zinc ions and dewatered swine manure-derived biochar on anaerobic digestion of swine wastewater - Gaojun Wang; Changxi Sun; Peng Fu; Bo Zhang; Jinglin Zhu; Qian Li; Jianfeng Zhang; Rong Chen (Environmental Research, 2024)

Enhancing flame retardancy, mechanical durability, and anti-aging property of polyurethane foam via novel cyclic phosphonate - Zhi-Cheng Fu; Fa-Yang Bu; Zhe-Peng Li; Ting Wang; Jin-Ni Deng; Hai-Bo Zhao; Sheng-Chao Huang; Yu-Zhong Wang; Ming-Jun Chen (Chemical Engineering Journal, 2024)

Solar-driven biomass chemical looping gasification using Fe3O4 for syngas and high-purity hydrogen production - Dequan Xu; Bo Wang; Xian Li; Yoke Wang Cheng; Wenming Fu; Yanjun Dai; Chi-Hwa Wang (Chemical Engineering Journal, 2024)

4-Hydroxybenzenesulfonic acid triggers rapid preparation of phenolic aerogel composites by ambient pressure drying - Xi Zhao; Lin Chen; Peng-Gang Su; Lin-Xi Xiao; Hai-Bo Zhao; Teng Fu; Xiu-Li Wang; Yu-Zhong Wang (Chemical Engineering Journal, 2024)

A multitemporal snow-covered remote sensing image matching method considering global and contextual features - Jian Zhang; Zhitao Fu; Shaochen Zhang; Ruihong Li; Bo-Hui Tang (International Journal of Remote Sensing, 2023)

Targeted degradation of naphthalene by peroxymonosulfate activation using molecularly imprinted biochar - Xueji You; Chaomeng Dai; Zeyu Wang; Yanping Duan; Jun Bo Zhang; Xiaoying Lai; Jiajun Hu; Jixiang Li; Maisideke Maimaitijiang; Yalei Zhang; Shuguang Liu; Rongbing Fu (Chemosphere, 2023)

Oxidation and side-chain modifications decrease gastrointestinal digestibility and transport of proteins from salted bighead carp fillets after frozen storage - Song Gao; Zixin Fu; Longteng Zhang; Bo Li; Yuqing Tan; Hui Hong; Yongkang Luo (Food Chemistry, 2023)

A Reactive Transport Model Considering the Bioavailability of PAHs Based on Lagrangian Reactive Particle-Tracking Method - Tao Chen; Wenbiao Huang; Yafu Zhang; Yanli Dong; Bo Fu; Haiyan Li (Water, Air, & Soil Pollution, 2023)

Observations on the embryonic development of the mud crab, Scylla paramamosain - Li-Kun Xu; Ke-Yi Ma; Feng-Ying Zhang; Wei Wang; Ling-Bo Ma; Zhong-Wen Jin; Ming Zhao; Wei Chen; Yin Fu; Chun-Yan Ma; Zhi-Qiang Liu (Frontiers in Marine Science, 2023)
To investigate the embryonic development of the mud crab Scylla paramamosain , we analyzed three critical parameters: egg color of, embryo morphology (through conventional and laser scanning confocal microscopy), and the distribution of cell divisions. During embryonic development, the egg color exhibited a progressive transition, shifting from orange to reddish-orange, then to brown, before ultimately darkening to black. Each embryo displayed a spherical shape, measuring approximately 280 μm in diameter, characterized by a smooth surface devoid of any depressions. The embryonic cell division was in the form of mixed oogenesis, comprised of complete division in the early stage, spiral oogenesis in the middle stage and surface division in the late stage. It is noteworthy that the blastopore appeared at the position where the transparent area and cell aggregation just appeared under the microscope, and the blastomere was a characteristic of the embryo entering the gastrulation stage. After entering the gastrulation stage, the cells aggregated towards the blastopore and formed two symmetrical cell clusters, which formed a V-shape with the void of the classic blastopore. When the transparent region occupied approximately 1/5 of the embryo ’ s volume, the embryo entered the nauplius stage, and the thoracic and abdominal armor, as well as the optic lobe and abdominal limb primordia, could be clearly distinguished. The appearance of the compound eye pigment band indicated the stage of compound eye pigment formation. At this time, the transparent area accounted for 1/4 of the embryo and a large number of ganglia appeared. The change of the compound eye pigment band from red to black was also one of the reasons for the blackening of the egg color of the crabs. The data obtained through this study have potential applications in the determination of embryonic development status and obtaining of high-quality seeds for S. paramamosain culture.

Numerical simulation of flow instability induced by a fixed cylinder placed near a plane wall in oscillating flow - Zi-Fang Li; Jiang-Hua Li; Jian-Zhao Wu; Kai-Leong Chong; Bo-Fu Wang; Quan Zhou; Yu-Lu Liu (Ocean Engineering, 2023)

Rate-dependent strength and crack damage thresholds of rocks at intermediate strain rate - Haibo Li; Liwang Liu; Shuaiyang Fu; Bo Liu; Xiaofeng Li (International Journal of Rock Mechanics and Mining Sciences, 2023)

Carbonate lithium isotope systematics indicate cooling triggered mass extinction during the Frasnian-Famennian transition - Yang-Yang Wang; Kun Liang; Yilin Xiao; Bo Chen; Erhao Shan; Tingyu Yang; Meng Zhang; He Sun; Hai-Ou Gu; Fengtai Tong; Lulu Fu; Dong-Yong Li; et al. (Global and Planetary Change, 2023)

Structural and gelling properties of whey proteins influenced by various acids: Experimental and computational approaches - Linlin Zhang; Zhuo Zhang; Stephen R. Euston; Bo Li; Erhu Li; Caixia Fu; Guodong Chen (Food Hydrocolloids, 2023)

Biochar facilitates methanogens evolution by enhancing extracellular electron transfer to boost anaerobic digestion of swine manure under ammonia stress - Gaojun Wang; Peng Fu; Bo Zhang; Ji Zhang; Qiuyi Huang; Gaofei Yao; Qian Li; Mawuli Dzakpasu; Jianfeng Zhang; Yu-You Li; Rong Chen (Bioresource Technology, 2023)

Leopard predation on wild Sichuan snub-nosed monkeys - Bin Yang; James R. Anderson; Ni-Na Gou; Jun Luo; Bo Hong; Wei-Wei Fu; Yong-Feng Chen; Wei-Feng Wang; Bao-Jia Cao; Shi-Yu Chen; Kai-Feng Wang; Bao-Guo Li (Primates, 2023)

Nanopore Structure and Multifractal Characteristics of Continental Shale Oil Reservoir: A Case Study from Ziliujing Shales in the Sichuan Basin - Youzhi Wang; Wei Li; Xiandong Wang; Zhiguo Wang; Weiqi Ma; Yanping Zhu; Mengdi Sun; Bo Liu; Lijuan Cheng; Xiaofei Fu (Journal of Marine Science and Engineering, 2023)
Thermal maturity of the shales from the Ziliujing Formation of the Jurassic age in the Sichuan Basin is in the hydrocarbon generation window, which makes it a candidate for shale oil and gas development. The meso- and macropore characteristics and heterogeneity of shales are important factors affecting the occurrence and development of oil and gas. However, the meso- and macropores of the Ziliujing shales have not been systematically studied. Thus, the mineral compositions and total organic carbon (TOC) of samples from this formation, as well as its pore structure, are analyzed by low-temperature N2 adsorption technique. Moreover, the heterogeneity of the pores was determined by multifractal analysis. The results show that the Ziliujing shales can be classified into three types according to the distributions of mineral compositions of carbonate and mixed and argillaceous shales. Results revealed that the smallest meso- and macropore volume (PV), the smallest specific surface area (SSA), and the largest average pore diameter (APD) occur in the carbonate shales. However, the largest PV and SSA and the smallest APD are observed in the argillaceous shales. The porosity of carbonate shales is mainly concentrated between 5 nm and 30 nm. Compared with carbonate shales, the porosity with pore sizes less than 30 nm of mixed and argillaceous shales shows a rapid increase. Furthermore, inorganic minerals are the main factors affecting the pore distributions, while TOC shows a weak effect. Herein, clay minerals significantly increase the mesopore volume and the pore number with a size of less than 30 nm. The Dq-q curves reveal that the meso- and macropore distributions of Ziliujing shales show multifractal behavior, but the multifractal characteristics of pores of various shales are distinctly different. The information dimension D1, the Hurst exponent H, and the width of the right side D0–D10 are key indicators to distinguish the local variations within the pore structure of different types of shales. The carbonate shales have the largest multifractal spectra width and the smallest D1 and H, while the opposite trend is found for the argillaceous shales. Clay minerals reduce the heterogeneity of the meso- and macropore distributions and increase the pore connectivity. Nevertheless, the carbonate minerals exhibit a reverse trend. Finally, it was found that TOC does not impact pore complexity as much. Collectively, this study supports our understanding of the occurrence of shale oil within various reservoir facies, thereby providing a guideline for future explorations in the Ziliujing Formation of the Jurassic age in the Sichuan Basin.

Resource utilization of rice straw to prepare biochar as peroxymonosulfate activator for naphthalene removal: Performances, mechanisms, environmental impact and applicability in groundwater - Jun Bo Zhang; Chaomeng Dai; Zeyu Wang; Xueji You; Yanping Duan; Xiaoying Lai; Rongbing Fu; Yalei Zhang; Maisideke Maimaitijiang; Kah Hon Leong; Yaojen Tu; Zhi Li (Water Research, 2023)

Influences of humic acids released during sludge thermal hydrolysis on anaerobic digestion: New insights from enzymatic perspectives - Fang Huang; Hongbo Liu; Jiaxin Wen; Shan Huang; Zhiyong Zheng; Xuedong Zhang; Bo Fu; Yajie Li; Aijie Wang; He Liu (Chemical Engineering Journal, 2023)

Semiconductors modified gourd-shaped hollow PtNi and their directional electron and mass transfer effects - Fu-Fei Pu; Yu-Xuan Xiao; Xiong Yang; Fei Yu; Lei Xia; Jiang-Bo Chen; Lu Wu; Jing-Jing Xie; Wen-Ying Zhao; Yu Liu; Li-Ying Wang; Jie Ying; et al. (Chemical Engineering Journal, 2023)

Triplet chromophoric dissolved organic matter regulating the phototransformation and toxicity of imidacloprid in paddy water - Yu Zeng; Qinglong Fu; Dionysios D. Dionysiou; Mingyang Zhang; Mabo Li; Bo Ye; Ning Chen; Juan Gao; Yujun Wang; Dongmei Zhou; Guodong Fang (Chemical Engineering Journal, 2023)

Geochronology and petrogenesis of the early Silurian Zeluo mafic-ultramafic intrusion, eastern Tibet: implications for the tectonic setting and evolution of the eastern Proto-Tethys Ocean - Hang Zhou; Wenxiao Zhou; Ernest Chi Fru; Thomas C. Sheldrick; Haiquan Li; Bo Huang; Dong Fu; Yadong Xu (International Geology Review, 2023)

TIPS: A three-dimensional phenotypic measurement system for individual maize tassel based on TreeQSM - Bo Xu; Xiangyuan Wan; Hao Yang; Haikuan Feng; Yuanyuan Fu; Haiyan Cen; Binbin Wang; Zhoufeng Zhang; Siyuan Li; Chunjiang Zhao; Guijun Yang (Computers and Electronics in Agriculture, 2023)

A non-toxic recombinant Clostridium septicum α toxin induces protective immunity in mice and rabbits - Jige Du; Irene Meki; Qianlin Li; Ying Liu; Zhen Zhu; Chenfan Pan; Yingju Xia; Lizhi Fu; Liu Yang; Suhui Zhang; Chunsheng Yin; Yufeng Luo; et al. (Toxicon, 2023)

Simulation of Rayleigh convection during dichloromethane absorption by water using lattice Boltzmann method - Ruixue Xiao; Kefan Chao; Ju Liu; Li Wang; Muhua Chen; Xinbao Zhu; Bo Fu (Process Safety and Environmental Protection, 2023)

Phase-mediated mercury removal from water using multilayered molybdenum disulfide: The key role of redox mechanism - Jia Sun; Junjun Pei; Zhiyuan Qiu; Jing Guo; Bo Li; Kaixing Fu; Kai Yin; Shenglian Luo (Journal of Cleaner Production, 2023)

The complexes of soybean protein isolate and procyanidin B2 have synergistic hypolipidemic activity at the cellular level by activating the AMPKα pathway - Lei Ji; Hongling Fu; Yi Wang; Jiaxin Li; Xiaoqing Yang; Hao Gong; Xiangze Meng; Wendan Jing; Weichang Dai; Youbao Li; Bo Lyu; Hansong Yu (Food Chemistry, 2023)

Structure, physicochemical and functional properties of plant-based SPI films from different soybean varieties deficient in β-conglycinin subunits - Jiaxin Li; Khalid Amin; Hongling Fu; Lei Ji; Yi Wang; Hao Gong; Hansong Yu; Bo Lyu; Xiaoqing Yang (Food Packaging and Shelf Life, 2023)

Structural analysis of shield machine cutting monopile using p-y curve based finite element method - Ting Li; Bo Liu; Yanhui Han; Chunqing Fu; Yanding Sun (Computers and Geotechnics, 2023)

Cenozoic basement-involved rifting of the northern South China Sea margin - Yanhui Suo; Sanzhong Li; Guangrong Peng; Xiaodong Du; Jie Zhou; Pengcheng Wang; Guangzeng Wang; Ian Somerville; Yixiao Diao; Zhongqiang Liu; Xinjian Fu; Bo Liu; et al. (Gondwana Research, 2023)

A study on the analysis of dynamical transmission behavior and mining key monitoring stations in PM and O3 networks in the Beijing-Tianjin-Hebei region of China - Xiaofei Shi; Bo Li; Donglei Fu; Jiao Bai; Stephen Dauda Yabo; Kun Wang; Xiaoxiao Gao; Jie Ding; Hong Qi (Environmental Research, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

The role of GLUT2 in glucose metabolism in multiple organs and tissues - Bo Sun; Hui Chen; Jisu Xue; Peiwu Li; Xu Fu (Molecular Biology Reports, 2023)
The glucose transporter family has an important role in the initial stage of glucose metabolism; Glucose transporters 2 (GLUTs, encoded by the solute carrier family 2, SLC2A genes) is the major glucose transporter in β-cells of pancreatic islets and hepatocytes but is also expressed in the small intestine, kidneys, and central nervous system; GLUT2 has a relatively low affinity to glucose. Under physiological conditions, GLUT2 transports glucose into cells and allows the glucose concentration to reach balance on the bilateral sides of the cellular membrane; Variation of GLUT2 is associated with various endocrine and metabolic disorders; In this study, we discussed the role of GLUT2 in participating in glucose metabolism and regulation in multiple organs and tissues and its effects on maintaining glucose homeostasis.

Nitrogen species and microbial community coevolution along groundwater flowpath in the southwest of Poyang Lake area, China - Xianglong Chen; Guangcai Wang; Yizhi Sheng; Fu Liao; Hairu Mao; Bo Li; Hongyu Zhang; Zhiyuan Qiao; Jiahui He; Yingxue Liu; Yilun Lin; Ying Yang (Chemosphere, 2023)

Effect of humic acid-modified attapulgite on polycyclic aromatic hydrocarbon adsorption and release from paddy soil into the overlying water in a rice-crab coculture paddy ecosystem and the underlying process - Nan Sun; Jin Liu; Bo-Wei Qi; Li-Li Lu; Hui-Ling Du; Shuang Li; Chang-Qing Li; Si-Wen Jiang; Zi-Jian Wang; An-Pei Yang; Guang-Lei Zhu; Tian-Yi Wang; et al. (Chemosphere, 2023)

Bifunctional reduced graphene oxide/polyelectrolyte/NiFe layered double hydroxide composites for efficient catalyzed dephosphorylation and 4-nitrophenol reduction - Zijun Xie; Bo Sun; Hongying Lin; Meng Fu; Yi Zhang; Zequn Ma; Xiangming Li (Journal of Water Process Engineering, 2023)

Occurrence, distribution, and risk assessment of quinolone antibiotics in municipal sewage sludges throughout China - Fan Meng; Shaojing Sun; Jialu Geng; Lixin Ma; Jinpan Jiang; Bo Li; Stephen Dauda Yabo; Lu Lu; Donglei Fu; Jimin Shen; Hong Qi (Journal of Hazardous Materials, 2023)

Uncovering quality changes of salted bighead carp fillets during frozen storage: The potential role of time-dependent protein denaturation and oxidation - Song Gao; Yueyue Liu; Zixin Fu; Huijuan Zhang; Longteng Zhang; Bo Li; Yuqing Tan; Hui Hong; Yongkang Luo (Food Chemistry, 2023)

Polymorphism analysis of major histocompatibility complex (MHC) DQB gene in the Asiatic black bear (Ursus thibetanus) - Yutian Jia; Qiang Fu; Bo Li; Yanchun Xu; Ahmad Tariq (Mammal Research, 2023)

Influence on the levels of PAHs and methylated PAHs in surface soil from pollution control in China: Evidence in 2019 data compared with 2005 and 2012 data - Fu-Jie Zhu; Zi-Feng Zhang; Li-Yan Liu; Hong Yao; Hong-Liang Jia; Zhi Zhang; Song Cui; Bo Meng; Gang Cao; Peng-Hao Su; Xiao-Xuan Mao; Bao-Long Li; et al. (Science of The Total Environment, 2023)

Complete biodegradation of the oldest organic herbicide 2,4-Dichlorophenoxyacetic acid by engineering Escherichia coli - Yu Wang; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Hong-Juan Han; Li-Juan Wang; Wen-Hui Zhang; Yong-Dong Deng; Cen Qian; Zhi-Hao Zuo; et al. (Journal of Hazardous Materials, 2023)

Gestational cadmium exposure disrupts fetal liver development via repressing estrogen biosynthesis in placental trophoblasts - Yi-Ting Fu; Jin Zhang; Wei-Bo Liu; Yu-Feng Zhang; Shuang Zhang; Lu-Lu Tan; Qing Lin; Kong-Wen Ou-Yang; Yong-Wei Xiong; Wei Chang; Hao Li; Jun-Ying Yu; et al. (Food and Chemical Toxicology, 2023)

Global ocean reanalysis CORA2 and its inter comparison with a set of other reanalysis products - Hongli Fu; Bo Dan; Zhigang Gao; Xinrong Wu; Guofang Chao; Lianxin Zhang; Yinquan Zhang; Kexiu Liu; Xiaoshuang Zhang; Wei Li (Frontiers in Marine Science, 2023)
We present the China Ocean ReAnalysis version 2 (CORA2) in this paper. We compare CORA2 with its predecessor, CORA1, and with other ocean reanalysis products created between 2004 and 2019 [GLORYS12v1 (Global Ocean reanalysis and Simulation), HYCOM (HYbrid Coordinate Ocean Model), GREP (Global ocean Reanalysis Ensemble Product), SODA3 (Simple Ocean Data Assimilation, version 3), and ECCO4 (Estimating the Circulation and Climate of the Ocean, version 4)], to demonstrate its improvements and reliability. In addition to providing tide and sea ice signals, the accuracy and eddy kinetic energy (EKE) of CORA2 are also improved owing to an enhanced resolution of 9 km and updated data assimilation scheme compared with CORA1. Error analysis shows that the root-mean-square error (RMSE) of CORA2 sea-surface temperature (SST) remains around 0.3°C, which is comparable to that of GREP and smaller than those of the other products studied. The subsurface temperature (salinity) RMSE of CORA2, at 0.87°C (0.15 psu), is comparable to that of SODA3, smaller than that of ECCO4, and larger than those of GLORYS12v1, HYCOM, and GREP. CORA2 and GLORYS12v1 can better represent sub-monthly-scale variations in subsurface temperature and salinity than the other products. Although the correlation coefficient of sea-level anomaly (SLA) in CORA2 does not exceed 0.8 in the whole region, as those of GREP and GLORYS12v1 do, it is more effective than ECCO4 and SODA3 in the Indian Ocean and Pacific Ocean. CORA2 can reproduce the variations in steric sea level and ocean heat content (OHC) on the multiple timescales as the other products. The linear trend of the steric sea level of CORA2 is closer to that of GREP than that of the other products, and the long-term warming trends of global OHC in the high-resolution CORA2 and GLORYS12v1 are greater than those in the low-resolution EN4 and GREP. Although CORA2 shows overall poorer performance in the Atlantic Ocean, it still achieves good results from 2009 onward. We plan to further improve CORA2 by assimilating the best available observation data using the incremental analysis update (IAU) procedure and improving the SLA assimilation method.

The development process of plant-based meat alternatives: Raw material formulations and processing strategies - Yi Wang; Bo Lyu; Hongling Fu; Jiaxin Li; Lei Ji; Hao Gong; Ruining Zhang; Jingsheng Liu; Hansong Yu (Food Research International, 2023)

The effects of pulsed electric fields treatment on the structure and physicochemical properties of dialdehyde starch - Ying Li; Jin-Hua Wang; Yu Han; Fu-Hao Yue; Xin-An Zeng; Bo-Ru Chen; Man-Qin Zeng; Meng-Wai Woo; Zhong Han (Food Chemistry, 2023)

Improving short-term streamflow forecasting by flow mode clustering - Shuqi Liu; Xinzhi Zhou; Bo Li; Xin He; Yuexin Zhang; Yi Fu (Stochastic Environmental Research and Risk Assessment, 2023)

Chemiluminescence Immunoassay Method of Urinary Liver Fatty-acid-binding Protein as a Promising Candidate for Kidney Disease - Lisong Niu; Lanya Li; Jinshan Li; Zhitian Chen; Jiayuan Lin; Bo Zhang; Xiaoling Fu (Journal of Fluorescence, 2023)

Apoptosis-related long non-coding RNA LINC5438 of Bombyx mori promotes the proliferation of BmNPV - Peng Chen; Min Cai; Yu-Jie Feng; Cong Li; Zhan-Qi Dong; Wen-Fu Xiao; Liang Tang; Yan Zhu; Ting Tian; Bo-Yuan Deng; Min-Hui Pan; Cheng Lu (Pesticide Biochemistry and Physiology, 2023)

Zircon SHRIMP U–Pb geochronology, geochemistry, and geological significance of dacite in the Zhesang gold district, southeast Yunnan Province, China - Bo Wang; Jiasheng Wang; Jinlong Li; Hao Fu; Yuehua Ma; Bin Ye (Acta Geochimica, 2023)

Synergistic interactions of fine particles and radiative effects in modulating urban heat islands during winter haze event in a cold megacity of Northeast China - Stephen Dauda Yabo; Donglei Fu; Bo Li; Lixin Ma; Xiaofei Shi; Lu Lu; Xie Shengjin; Fan Meng; Jinpan Jiang; Wei Zhang; Hong Qi (Environmental Science and Pollution Research, 2023)

Deciphering the role and mechanism of nano zero-valent iron on medium chain fatty acids production from CO2 via chain elongation in microbial electrosynthesis - Ping Wu; Jie Zhang; Jing Li; Yan Zhang; Bo Fu; Ming-Yi Xu; Yi-Feng Zhang; He Liu (Science of The Total Environment, 2023)

Spatial variability of source contributions to nitrate in regional groundwater based on the positive matrix factorization and Bayesian model - Hairu Mao; Guangcai Wang; Fu Liao; Zheming Shi; Hongyu Zhang; Xianglong Chen; Zhiyuan Qiao; Bo Li; Yunfei Bai (Journal of Hazardous Materials, 2023)

Why did air quality experience little improvement during the COVID-19 lockdown in megacities, northeast China? - Donglei Fu; Xiaofei Shi; Jinxiang Zuo; Stephen Dauda Yabo; Jixiang Li; Bo Li; Haizhi Li; Lu Lu; Bo Tang; Hong Qi; Jianmin Ma (Environmental Research, 2023)

Acute Aluminum Sulfate Triggers Inflammation and Oxidative Stress, Inducing Tissue Damage in the Kidney of the Chick - Bo Chen; Lina Chen; Zhiqing Yang; Qiang Fu; Xinran Li; Changyu Cao (Biological Trace Element Research, 2023)

Detection of polycyclic aromatic hydrocarbons using a high performance-single particle aerosol mass spectrometer - Yao Zhang; Chenglei Pei; Jinwen Zhang; Chunlei Cheng; Xiufeng Lian; Mubai Chen; Bo Huang; Zhong Fu; Zhen Zhou; Mei Li (Journal of Environmental Sciences, 2023)

Analysis of lunar wrinkle ridges regarding the maximum displacement–length scaling relationship and relevant geological factors - Chenfan Li; Bo Li; Xiaohui Fu; Le Qiao; Zongcheng Ling; Jianguo Yan; Shaojie Qu; Shengbo Chen (Icarus, 2023)

Bioaccumulation and emission of organophosphate esters in plants affecting the atmosphere's phosphorus cycle - Shengxing Long; Paul B. Hamilton; Bo Fu; Jing Xu; Luchao Han; Xinhao Suo; Yuqin Lai; Guofeng Shen; Fuliu Xu; Bengang Li (Environmental Pollution, 2023)

Geraniin targeting CaMKK2 inhibits lipid accumulation in 3T3-L1 adipocytes by suppressing lipogenesis - Ji Li; Xuedong Wang; Xiangyu Meng; Xin Zhou; Han Huang; Yi Feng; Yujie Fu; Xinxin Liu; Bo Yu (Chemico-Biological Interactions, 2023)

Multi-source Data-driven Identification of Urban Functional Areas: A Case of Shenyang, China - Bing Xue; Xiao Xiao; Jingzhong Li; Bingyu Zhao; Bo Fu (Chinese Geographical Science, 2023)

Phosphorus availability mediates plant–plant interaction and field productivity in maize-grass pea intercropping system: Field experiment and its global validation - Shuang-Guo Zhu; Hong-Yan Tao; Wen-Bo Li; Rui Zhou; Yan-Wen Gui; Li Zhu; Xiao-Lin Zhang; Wei Wang; Bao-Zhong Wang; Fu-Jian Mei; Hao Zhu; You-Cai Xiong (Agricultural Systems, 2023)

Pathology, Enzyme Activity and Immune Responses after Cryptocaryon irritans Infection of Golden Pompano Trachinotus ovatus (Linnaeus 1758) - Hua-Yang Guo; Wen-Fu Li; Ke-Cheng Zhu; Bao-Suo Liu; Nan Zhang; Bo Liu; Jing-Wen Yang; Dian-Chang Zhang (Journal of Marine Science and Engineering, 2023)
Golden pompano (Trachinotus ovatus) has become an economically important fish in China in the past decade. However, Cryptocaryon irritans, a parasitic ciliate, causes considerable economic losses in the mariculture of T. ovatus. To characterize the pathogenesis of C. irritans in T. ovatus, the pathological properties, immune-related enzyme activity and expression of the NEMO gene was analysed. The results from the histological sections showed that there was considerable metamorphosis and hyperplasia in the parasitized sites (skin) with leukocyte aggregation and mucous cell increases after C. irritans infection. Moreover, the activities of four enzymes, that is, alkaline phosphatase (AKP), acid phosphatase (ACP), superoxide dismutase (SOD) and lysozyme (LZM), were significantly increased in different tissues after C. irritans infection. Furthermore, the ORF of T. ovatus NF-kappa-B essential modulator (ToNEMO) measures 1650 bp, encoding 548 amino acids. The ToNEMO transcripts were universally expressed in all examined tissues, with higher levels being observed in the immune-relevant and central nervous tissues. The mRNA levels of ToNEMO after C. irritans infection were significantly increased in the gill, skin, liver, spleen and head kidney. These results suggested that ToNEMO might be involved in immune responses and helped to elucidate the physiological response after the C. irritans infection of fish.

The source distribution and seasonal discrepancies of antibiotic resistance genes among multiple environment media in a cold megacity - Fan Meng; Shaojing Sun; Jialu Geng; Lixin Ma; Jinpan Jiang; Bo Li; Stephen Dauda Yabo; Lu Lu; Donglei Fu; Jimin Shen; Hong Qi (Journal of Cleaner Production, 2023)

The heated-induced gelation of soy protein isolate at subunit level: Exploring the impacts of α and α′ subunits on SPI gelation based on natural hybrid breeding varieties - Hongling Fu; Jiaxin Li; Xiaoqing Yang; Mohammed Sharif Swallah; Hao Gong; Lei Ji; Xiangze Meng; Bo Lyu; Hansong Yu (Food Hydrocolloids, 2023)

Near-infrared I/II emission and absorption carbon dots via constructing localized excited/charge transfer state for multiphoton imaging and photothermal therapy - Wen-Bo Zhao; Dan-Dan Chen; Kai-Kai Liu; Yong Wang; Rui Zhou; Shi-Yu Song; Fu-Kui Li; Lai-Zhi Sui; Qing Lou; Lin Hou; Chong-Xin Shan (Chemical Engineering Journal, 2023)

Influence of thermal hydrolysis on sludge anaerobic digestion: Release of humic acid promotes electron transport of methanogen - Cheng Zhao; Hongbo Liu; He Liu; Xinmin Zhan; Xuedong Zhang; Bo Fu; Mingze Shi; Shuailing Lu; Fang Huang; Minhua Cui; Yajie Li (Chemical Engineering Journal, 2023)

The self-powered electrochemical biosensing platform with multi-amplification strategy for ultrasensitive detection of microRNA-155 - Yong-ping Gao; Ke-jing Huang; Fu-ting Wang; Yang-yang Hou; Lu-di Zhao; Bo-ya Wang; Jing Xu; Honglei Shuai; Guoqiang Li (Analytica Chimica Acta, 2023)

Separation of Panax notoginseng saponins on modified rosin ester-bonded silica stationary phase and its mechanism - Wen-Bo Xie; Hao Li; Lei Zeng; Li-Juan Jiang; Wen Li; Lu Xia; Fu-Hou Lei (Analytica Chimica Acta, 2023)

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

Impacts of Mercury Exposure Levels and Sources on the Demethylation of Methylmercury Through Human Gut Microbiota - Xian-Feng Yang; Shao-Chen Yang; Fu-Li Wen; Lin Feng; Bo Meng; Hai-Yan Hu; Bao-Lin Wang; Jun Li; Alexandre J. Poulain; Ping Li (Bulletin of Environmental Contamination and Toxicology, 2022)

Shaking table test and numerical analysis of single-layer reticulated domes with or without three-dimensional isolation bearing - Gui-Bo Nie; Dong-fang Li; Xu-dong Zhi; Fu-yang Wang; Chen-xiao Zhang (Bulletin of Earthquake Engineering, 2022)

Climate Warming Mitigation from Nationally Determined Contributions - Bo Fu; Jingyi Li; Thomas Gasser; Philippe Ciais; Shilong Piao; Shu Tao; Guofeng Shen; Yuqin Lai; Luchao Han; Bengang Li (Advances in Atmospheric Sciences, 2022)

Oct4 facilitates chondrogenic differentiation of mesenchymal stem cells by mediating CIP2A expression - Lexiang Li; Qiwei Fu; Jiahua Shao; Bo Wang; Zheru Ding; Shuai Yuan; Jinhui Peng; Wei Xin; Jun Zhu; Yi Chen (Cell and Tissue Research, 2022)

Impact of land cover transformation on urban heat islands in Harbin, China - Stephen Dauda Yabo; Donglei Fu; Bo Li; Xiaofei Shi; Samit Thapa; Xie Shengjin; Lu Lu; Hong Qi; Wei Zhang (Environmental Monitoring and Assessment, 2022)

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

Long Non-coding Antisense RNA DDIT4-AS1 Regulates Meningitic Escherichia coli-Induced Neuroinflammation by Promoting DDIT4 mRNA Stability - Bo Yang; Bojie Xu; Ruicheng Yang; Jiyang Fu; Liang Li; Dong Huo; Jiaqi Chen; Xiaopei Yang; Chen Tan; Huanchun Chen; Xiangru Wang (Molecular Neurobiology, 2022)
Our previous studies have shown that meningitic Escherichia coli can colonize the brain and cause neuroinflammation. Controlling the balance of inflammatory responses in the host central nervous system is particularly vital. Emerging evidence has shown the important regulatory roles of long non-coding RNAs (lncRNAs) in a wide range of biological and pathological processes. However, whether lncRNAs participate in the regulation of meningitic E. coli -mediated neuroinflammation remains unknown. In the present study, we characterized a cytoplasm-enriched antisense lncRNA DDIT4-AS1 , which showed similar concordant expression patterns with its parental mRNA DDIT4 upon E. coli infection. DDIT4-AS1 modulated DDIT4 expression at both mRNA and protein levels. Mechanistically, DDIT4-AS1 promoted the stability of DDIT4 mRNA through RNA duplex formation. DDIT4-AS1 knockdown and DDIT4 knockout both attenuated E. coli -induced NF-κB signaling as well as pro-inflammatory cytokines expression, and DDIT4-AS1 regulated the inflammatory response by targeting DDIT4 . In summary, our results show that DDIT4-AS1 promotes E. coli -induced neuroinflammatory responses by enhancing the stability of DDIT4 mRNA through RNA duplex formation, providing potential nucleic acid targets for new therapeutic interventions in the treatment of bacterial meningitis.

Neuroprotective effect of aldose reductase knockout in a mouse model of spinal cord injury involves NF-κB pathway - Fu-xin Han; Rui Zhang; Xin-xing Yang; Shan-bo Ma; Shi-jie Hu; Bing Li (Experimental Brain Research, 2022)

Petrogenesis of the Late Triassic Mengsong strongly peraluminous granites in the southeastern Tibetan Plateau: highly fractionated from crystal mush - Feng Cong; Fu-Yuan Wu; Wen-Chang Li; De-Feng He; Zai-Bo Sun; Xiao-Ming Huang; Zhi-Zhong Hu; Han Zhao (International Geology Review, 2022)

New paraconic acids from the endophytic fungus Xylariaceae sp. J4 - Chao Yuan; Xue-Chun Shu; Lin Fan; Ying-Bo Zhang; Ling-Liang Guan; Fu-Lai Yu; Xiao-Lu Chen; Gang Li (Natural Product Research, 2022)

A community effort to assess and improve computerized interpretation of 12-lead resting electrocardiogram - Zijian Ding; Guijin Wang; Huazhong Yang; Ping Zhang; Dapeng Fu; Zhen Yang; Xinkang Wang; Xia Wang; Zhourui Xia; Chiming Zhang; Wenjie Cai; Binhang Yuan; et al. (Medical & Biological Engineering & Computing, 2022)
Computerized interpretation of electrocardiogram plays an important role in daily cardiovascular healthcare. However, inaccurate interpretations lead to misdiagnoses and delay proper treatments. In this work, we built a high-quality Chinese 12-lead resting electrocardiogram dataset with 15,357 records, and called for a community effort to improve the performances of CIE through the China ECG AI Contest 2019. This dataset covers most types of ECG interpretations, including the normal type, 8 common abnormal types, and the other type which includes both uncommon abnormal and noise signals. Based on the Contest, we systematically assessed and analyzed a set of top-performing methods, most of which are deep neural networks, with both their commonalities and characteristics. This study establishes the benchmarks for computerized interpretation of 12-lead resting electrocardiogram and provides insights for the development of new methods.

Identification of bacterial blight resistance genes in rice landraces from Yunnan Province, China - Caimei Zhao; Fuyou Yin; Ling Chen; Dingqin Li; Suqin Xiao; Qiaofang Zhong; Bo Wang; Xue Ke; Jian Fu; Xiang Li; Yue Chen; Lingxian Wang; et al. (Australasian Plant Pathology, 2022)
Bacterial blight (BB), a serious bacterial disease caused by pathogen Xanthomonas oryzae pv. oryzae ( Xoo ) affects rice growth and yield. Yunnan Province is regarded as a center of rice diversity in China and indeed the world, and has abundant rice landrace resources, which may offer prospective candidate donors in rice improvement and breeding. In this study, a set of 200 rice landraces were evaluated to determine their resistance to 10 pathogenic Xoo strains resistance by the leaf-clipping method. The results indicated that the tested rice landraces had different resistance levels against different Xoo strains. Multiple comparisons showed that the Xoo strain PXO99 was virulent to the tested rice landraces. Sixty-six rice landraces conferred resistance against at least one Xoo strain. These resistant rice landraces screened were then performed the presence of 14 cloned BB resistance genes by closely linked molecular markers and designed specific primers. The results showed that none of these resistant accessions contained xa13 , Xa21 , Xa27 , and Xa45(t) homologous fragments, while 9, 24, 4, 7, 9, 15, 1, 5, 4 and 27 accessions contained Xa1 , Xa2/Xa31(t) , Xa14 , Xa3/Xa26 , Xa4 , xa5 , Xa7 , Xa10 , Xa23 and xa25 homologous fragments, respectively. Sequence analysis further revealed that nucleotide variations around functional nucleotide polymorphisms region were observed within these accessions containing the Xa1 , Xa2/Xa31(t) , Xa14 , Xa3/Xa26 , Xa4 , xa5 , Xa10 , Xa23 and xa25 homologous fragments. These results along with phenotypic resistance spectrum supported that these accessions carried nine resistance homologous genes. Only one accession (Qishanggu_Wenshan) carried the Xa7 resistance gene. We also found that some resistant rice landraces, especially Xilandigu_Baoshan, and Laoyaling_Lincang without the above resistance genes, which mediated broad spectrum resistance to multiple Xoo strains, were identified as potential sources for breeding rice lines resistance to BB.

A novel alphahypovirus that infects the fungal plant pathogen Sclerotinia sclerotiorum - Weibo Liang; Zhongbo Lu; Jie Duan; Daohong Jiang; Jiatao Xie; Jiasen Cheng; Yanping Fu; Tao Chen; Bo Li; Xiao Yu; Weidong Chen; Yang Lin (Archives of Virology, 2022)

Intra-annual radial growth and its climate response for Masson pine and Chinese fir in subtropical China - Shengwang Meng; Xiaoli Fu; Bo Zhao; Xiaoqin Dai; Qingkang Li; Fengting Yang; Liang Kou; Huimin Wang (Trees, 2021)

Degraded polysaccharides from Porphyra haitanensis: purification, physico-chemical properties, antioxidant and immunomodulatory activities - Yun-Feng Huo; Yin-Ting Li; Wei Xia; Chong Wang; Yuan-Yuan Xie; Yan-Bo Wang; Tao Zhou; Ling-Lin Fu (Glycoconjugate Journal, 2021)

Descending Modulation of Spinal Itch Transmission by Primary Somatosensory Cortex - Zi-Han Wu; Han-Yu Shao; Yuan-Yuan Fu; Xiao-Bo Wu; De-Li Cao; Sheng-Xiang Yan; Wei-Lin Sha; Yong-Jing Gao; Zhi-Jun Zhang (Neuroscience Bulletin, 2021)

Impact of climate change on snowmelt runoff in a Himalayan basin, Nepal - Samit Thapa; Haizhi Li; Bo Li; Donglei Fu; Xiaofei Shi; Stephen Yabo; Lu Lu; Hong Qi; Wei Zhang (Environmental Monitoring and Assessment, 2021)

Lignin Synthesis Related Genes with Potential Significance in the Response of Upland Cotton to Fusarium Wilt Identified by Transcriptome Profiling - Jianan Hou; Fu’an Zhao; Xiaojie Yang; Wu Li; Deyi Xie; Zhongjie Tang; Shuping Lv; Lihong Nie; Yao Sun; Mengmeng Wang; Yajing Zhu; Xiaopei Bo; et al. (Tropical Plant Biology, 2021)
Fusarium wilt, caused by the fungus Fusarium oxysporum Schlecht. f. sp. vasinfectum (Fov) is a destructive soil-borne cotton disease. To profile the genes and pathways responding to Fov infection, we compared transcriptomic responses before and after F. oxysporum inoculation in a highly resistant cotton cultivar, Yumian21, and a highly susceptible cultivar, Jimian11. Although the overall gene expression pattern was downregulated in both cultivars, the global gene expression in the resistant cultivar was stronger than that in the susceptible cultivar. In addition, the expressed genes of two cultivars mostly differed in “cellular process,” “single-organism process,” “metabolic process,” and “response to stimulus” functional groups in the biological process Gene Ontology category: the upregulated differentially expressed genes (DEG) were largely enriched in the resistant cultivar, while the downregulated DEGs were largely enriched in the susceptible cultivar. Phenylpropanoid biosynthesis and phenylalanine metabolism are the key metabolic pathways in cotton in response to Fov. We found that lignin plays a potential role in cotton resistance to Fov. Two coding genes, caffeic acid 3-O-methyltransferase and peroxidase2 , as well as the two transcription factors MYB46 and MYB86 , are possibly involved in the accumulation and synthesis of lignin. Furthermore, the result showed that the quantification of lignin could be potentially used as a selection tool to identify Fusarium wilt resistant cotton.

Effects of Spray Parameters on the Effective Spray Width of Single-Rotor Drone in Sugarcane Plant Protection - Ping Zhang; Wei Zhang; Hai-Tian Sun; Feng-Guang He; Hai-Ba Fu; Li-Qiang Qi; Li-Juan Yu; Li-Yu Jin; Bo Zhang; Jian-Sheng Liu (Sugar Tech, 2021)

The MYB transcription factor Baymax1 plays a critical role in rice male fertility - Xiao-Jiao Xiang; Lian-Ping Sun; Ping Yu; Zheng-Fu Yang; Pei-Pei Zhang; Ying-Xin Zhang; Wei-Xun Wu; Dai-Bo Chen; Xiao-Deng Zhan; Riaz-Muhammad Khan; Adil Abbas; Shi-Hua Cheng; et al. (Theoretical and Applied Genetics, 2021)

Melatonin ameliorates spatial memory and motor deficits via preserving the integrity of cortical and hippocampal dendritic spine morphology in mice with neurotrauma - Xiao-Jing Lin; Ruoxu Liu; Chenyi Li; Xueqing Yi; Bo Fu; M. J. Walker; Xiao-Ming Xu; Gang Sun; Cheng-Hsien Lin (Inflammopharmacology, 2020)

Characteristics of methane emissions in the Living Water Garden in Chengdu City from 2012 to 2017 - Ru Xue; Xiaoling Liu; Xiaoying Fu; Hongbing Luo; Ke Zhang; Bruce C. Anderson; Mei Li; Bo Huang; Lijuan Yu; Xiaoting Li; Shuzhi Fu; Aiping Pu; et al. (Environmental Science and Pollution Research, 2020)

Elastic wave propagation and scattering in prestressed porous rocks - Li-Yun Fu; Bo-Ye Fu; Weijia Sun; Tongcheng Han; Jianlin Liu (Science China Earth Sciences, 2020)

Dynamic Change of Shanks Gene mRNA Expression and DNA Methylation in Epileptic Rat Model and Human Patients - Yujiao Fu; Du Liu; Jialing Guo; Hongyu Long; Wenbiao Xiao; Wei Xiao; Li Feng; Zhaohui Luo; Bo Xiao (Molecular Neurobiology, 2020)

Characterization of viromes within mosquito species in China - Jiang Du; Fan Li; Yelin Han; Shihong Fu; Bo Liu; Nan Shao; Haoxiang Su; Weijia Zhang; Dandan Zheng; Wenwen Lei; Jie Dong; Lilian Sun; et al. (Science China Life Sciences, 2020)

Deformation characteristics and failure mechanism of a reactivated landslide in Leidashi, Sichuan, China, on August 6, 2019: an emergency investigation report - Weile Li; Bo Zhao; Qiang Xu; Fan Yang; Hao Fu; Cong Dai; Xinxin Wu (Landslides, 2020)

Design, synthesis and cholinesterase inhibitory activity of α -mangostin derivatives - Xiao-Qian Chi; Bo Hou; Liu Yang; Cheng-Ting Zi; Yong-Feng Lv; Jin-Yu Li; Fu-Cai Ren; Ming-Yan Yuan; Jiang-Miao Hu; Jun Zhou (Natural Product Research, 2020)

Trend analysis of climatic variables and their relation to snow cover and water availability in the Central Himalayas: a case study of Langtang Basin, Nepal - Samit Thapa; Bo Li; Donglei Fu; Xiaofei Shi; Bo Tang; Hong Qi; Kun Wang (Theoretical and Applied Climatology, 2020)

Synthesis and biological effects of naphthalene-chalcone derivatives - Qing-Hao Jin; Hong-Hai Chen; Wen-Bo Chen; Zhi-Yang Fu; Li-Ping Guan; Hai-Ying Jiang (Medicinal Chemistry Research, 2020)

Identification and Expression Pattern Analysis of Bacterial Blight Resistance Genes in Oryza officinalis Wall ex Watt Under Xanthomonas oryzae Pv. oryzae Stress - Chunmiao Jiang; Suqin Xiao; Dingqin Li; Ling Chen; Qiaofang Zhong; Fuyou Yin; Tengqiong Yu; Xue Ke; Dunyu Zhang; Jian Fu; Yue Chen; Bo Wang; et al. (Plant Molecular Biology Reporter, 2019)
Background Bacterial blight (BB) caused by Xanthomonas oryzae Pv. oryzae ( Xoo ) is one of the most serious diseases of rice worldwide. Oryza officinalis Wall ex Watt, harboring abundant genetic diversity and disease resistance features, are important resources of exploring resistance genes with broad-spectrum resistance to BB. However, the molecular mechanisms and genes of BB resistance in O. officinalis have been rarely explored. Results Here, the BB resistance of four different origin O. officinalis populations in Yunnan were identified by seven representative hypervirulent Xoo races, which exhibited different BB resistance among four populations, in which the BB resistance of the Gengma_Lincang population was the strongest. In addition, the pathogenetic ability of seven Xoo races to O. officinalis was different in that the pathogenicity of PXO99 was stronger than that of C5. There were no remarkable differences in leaf microstructures among four O. officinalis populations, revealing the differences in resistance of four O. officinalis to BB are caused by the endogenous resistance genes. Furthermore, our results proved that there were no nine cloned BB resistance genes in four populations but possessed dominant Xa5 , dominant Xa13 , and recessive xa3/xa26 homologous alleles of xa5 , xa13 , and Xa3 / Xa26 resistance genes. These three homologous genes were isolated and cloned from four populations and named OoXa5 , OoXa13 , and Ooxa3 / xa26 . The expression profile revealed that the expression levels of OoXa13 and Ooxa3/xa26 were significantly down-regulated under PXO99 and C5 stress, especially in the Gengma_Lincang population, suggesting the O. officinalis might enhance BB resistance by down-regulating the expression level of OoXa13 and Ooxa3 / xa26 . Conclusion The BB resistance genes of O. officinalis had its own characteristics by expression pattern and BLAST analysis of OoXa5 , OoXa13 , and Ooxa3 / xa26 , which indicated that there might be new genes or molecular mechanism of BB resistance in O. officinalis. Our studies provided a solid foundation and reference for revealing the molecular mechanism of BB resistance in O. officinalis .

Interception of sulfate deposition from a closed canopy to a forest gap edge canopy in a subalpine dragon spruce plantation - Yu Zhang; Fu-zhong Wu; Bo Tan; Zhen-feng Xu; Han Li; Jun-cheng Liu; Hai-rong Zhao; Si-yi Tan; Cheng-ming You; Wan-qin Yang (Journal of Mountain Science, 2019)

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

Electron Probe Microanalysis of Monazite and Its Applications to U-Th-Pb Dating of Geological Samples - Wenbin Ning; Junpeng Wang; Deng Xiao; Fenfang Li; Bo Huang; Dong Fu (Journal of Earth Science, 2019)

3D-Printed Wearable Personalized Orthodontic Retainers for Sustained Release of Clonidine Hydrochloride - Heliu Jiang; Junhui Fu; Mingguang Li; Shanshan Wang; Bo Zhuang; Haiyan Sun; Cheng Ge; Bin Feng; Yiguang Jin (AAPS PharmSciTech, 2019)

African Orphan Crops Consortium (AOCC): status of developing genomic resources for African orphan crops - Prasad S. Hendre; Samuel Muthemba; Robert Kariba; Alice Muchugi; Yuan Fu; Yue Chang; Bo Song; Huan Liu; Min Liu; Xuezhu Liao; Sunil Kumar Sahu; Sibo Wang; et al. (Planta, 2019)

Correction to: Chronic phencyclidine treatment impairs spatial working memory in rhesus monkeys - Bo Zhang; Fei Xiong; Yuanye Ma; Bing Li; Yu Mao; Zhu Zhou; Hualin Yu; JingHui Li; Chuanyu Li; Juan Fu; Jianhong Wang; Xudong Zhao (Psychopharmacology, 2019)

Chronic phencyclidine treatment impairs spatial working memory in rhesus monkeys - Bo Zhang; Fei Xiong; Yuanye Ma; Bing Li; Yu Mao; Zhu Zhou; Hualin Yu; JingHui Li; Chuanyu Li; Juan Fu; Jianhong Wang; Xudong Zhao (Psychopharmacology, 2019)

The associations of air pollution exposure during pregnancy with fetal growth and anthropometric measurements at birth: a systematic review and meta-analysis - Li Fu; Yi Chen; Xinyi Yang; Zuyao Yang; Sha Liu; Lei Pei; Baixiang Feng; Ganxiang Cao; Xin Liu; Hualiang Lin; Xing Li; Yufeng Ye; et al. (Environmental Science and Pollution Research, 2019)

Neural Differentiation of Mouse Neural Stem Cells as a Tool to Assess Developmental Neurotoxicity of Drinking Water in Taihu Lake - Yang Zhou; Yu Fu; Zhendong Bai; Peixin Li; Bo Zhao; Yuehua Han; Ting Xu; Ningyan Zhang; Lin Lin; Jian Cheng; Jun Zhang; Jing Zhang (Biological Trace Element Research, 2019)

Mitochondrial Gene Heterogeneity and Population Genetics of Haemaphysalis longicornis (Acari: Ixodidae) in China - Zhong-Bo Li; Yi-Tian Fu; Tian-Yin Cheng; Guo-Min Yao; Qiang-Hong Hou; Fen Li; Yu Zhao; Feng-Cai Zou; Guo-Hua Liu (Acta Parasitologica, 2019)

Metanephric mesenchyme-derived Foxd1+ mesangial precursor cells alleviate mesangial proliferative glomerulonephritis - Meiling Jin; Zhong Yin; Kai Wei; Yuansheng Xie; Xueyuan Bai; Bo Fu; Zhe Feng; Qinggang Li; Xiangmei Chen (Journal of Molecular Medicine, 2019)

Influence of provenance and shade on biomass production and triterpenoid accumulation in Cyclocarya paliurus - Bo Deng; Shengzuo Fang; Xulan Shang; Xiangxiang Fu; Yan Li (Agroforestry Systems, 2019)

Assembly and dispersal history of continental blocks within the Altun-Qilian-North Qaidam mountain belt, NW China - Changlei Fu; Zhen Yan; Xianqing Guo; Manlan Niu; Bo Cao; Qi Wu; Xiucai Li; Zongqi Wang (International Geology Review, 2019)

Luminescence chronology of the Palaeolithic–Neolithic transition in the Yujiagou site at the Nihewan Basin, northern China - Xue Rui; Yu‐Jie Guo; Jia‐Fu Zhang; Yue Hu; Hui‐Jie Mei; You‐Ping Wang; Fei Xie; Bo Li (Journal of Quaternary Science, 2019)
The relationship between the Palaeolithic–Neolithic cultural transition and environmental changes is important for understanding human history. However, the timing and nature of human behaviour at the transition, and their relationship to local environmental conditions, remain poorly understood. The Yujiagou archaeological site in the Nihewan Basin, northern China, provides valuable chronological and archaeological information about cultural changes in northern China due to its continuous archaeological sequence of cultural layers from the Palaeolithic to Neolithic. In this study, we apply post‐infrared infrared stimulated luminescence (pIRIR) dating on individual feldspar grains to date the Yujiagou deposits. We provide a revised chronology for the archaeological sequence at the site. We combine these results with multi‐proxy climatic indicators to gain insights into palaeoenvironmental changes in the region. The results show that the age of the artefact‐bearing deposits ranges from 13.5 to 9.7 ka. Polished stones and pottery begin to occur in the archaeological layer around 13 ka, corresponding to a transitional period when the local climate changed from cold to warm. This site provides evidence for understanding the process that led to the regional transition from hunter‐gathering to farming.

Reduced hsa-miR-124-3p levels are associated with the poor survival of patients with hepatocellular carcinoma - Hui-Deng Long; Yu-Shui Ma; Hui-Qiong Yang; Shao-Bo Xue; Ji-Bin Liu; Fei Yu; Zhong-Wei Lv; Ji-Yu Li; Ru-Ting Xie; Zheng-Yan Chang; Gai-Xia Lu; Wen-Ting Xie; et al. (Molecular Biology Reports, 2018)

Enzymatic gene expression by Pleurotus tuoliensis (Bailinggu): differential regulation under low temperature induction conditions - Shuang Hua; Bo Zhang; Yongping Fu; Bao Qi; Yanshuang Li; Fenghua Tian; Yu Li (World Journal of Microbiology and Biotechnology, 2018)

Spatiotemporal characteristics of earthquake disaster losses in China from 1993 to 2016 - Xiaoli Li; Zhiqiang Li; Jiansi Yang; Yaohui Liu; Bo Fu; Wenhua Qi; Xiwei Fan (Natural Hazards, 2018)

The relative abundance of alkane‐degrading bacteria oscillated similarly to a sinusoidal curve in an artificial ecosystem model from oil‐well products - Guoqiang Li; Peike Gao; Bo Zhi; Bing Fu; Ge Gao; Zhaohui Chen; Mengli Gao; Mengmeng Wu; Ting Ma (Environmental Microbiology, 2018)
Summary Microbial phylogenetic diversity and species interactions in natural ecosystems have been investigated extensively, but our knowledge about their ecological roles, community dynamics and succession patterns is far from complete. This knowledge is essential to understand the complicated interactions of microorganisms in natural ecosystems. Here, an artificial ecosystem model of microorganisms was constructed from oil‐well products and cultivated in a chemostat to investigate the succession pattern of alkane‐degrading bacteria, a functional population in oil reservoirs. Their abundance was quantified by an improved qPCR technique. Our results showed that the phylogenetic structure of this artificial ecosystem model is stable during most of the chemostat cultivation process, while the genotype structure of alkane‐degrading bacteria containing alk B genes shifted and their relative abundance oscillated similarly to a sinusoidal curve, like the succession pattern of producers in the Lotka–Volterra model. These results suggest that some theoretical frameworks of macroecology may work well in microbial ecosystems and be an efficient tool to understand them.

Host species effects on bacterial communities associated with the fruiting bodies of Tuber species from the Sichuan Province in Southwest China - Lei Ye; Qiang Li; Yu Fu; Pierre Sourzat; Hao Tan; Jie Zou; Bo Zhang; Xiaolin Li (Mycological Progress, 2018)

Microarray expression profiling and co-expression network analysis of circulating LncRNAs and mRNAs associated with neurotoxicity induced by BPA - Wei Pang; Fu-Zhi Lian; Xue Leng; Shu-min Wang; Yi-bo Li; Zi-yu Wang; Kai-ren Li; Zhi-xian Gao; Yu-gang Jiang (Environmental Science and Pollution Research, 2018)

Sp1 is an important transcriptional regulation factor for forkhead box N1 in pig - Dong Jie Zhang; Liang Wang; Zhong Qiu Li; Bo Fu; Guo Wei Yang; Di Liu (Journal of Genetics, 2018)

Molecular diversity of phenothiazines: design and synthesis of phenothiazine–dithiocarbamate hybrids as potential cell cycle blockers - Dong-Jun Fu; Ruo-Han Zhao; Jia-Huan Li; Jia-Jia Yang; Ruo-Wang Mao; Bo-Wen Wu; Ping Li; Xiao-Lin Zi; Qing-Qing Zhang; Hui-Jie Cai; Sai-Yang Zhang; Yan-Bing Zhang; et al. (Molecular Diversity, 2017)

Drought Alleviated the Negative Effects of Elevated O3 on Lonicera maackii in Urban Area - Sheng Xu; Wei Fu; Xingyuan He; Wei Chen; Weiwei Zhang; Bo Li; Yanqing Huang (Bulletin of Environmental Contamination and Toxicology, 2017)

Behavioural genetic differences between Chinese and European pigs - Qingpo Chu; Tingting Liang; Lingling Fu; Huizhi Li; Bo Zhou (Journal of Genetics, 2017)

Developing the science product algorithm testbed for Chinese next-generation geostationary meteorological satellites: Fengyun-4 series - Min Min; Chunqiang Wu; Chuan Li; Hui Liu; Na Xu; Xiao Wu; Lin Chen; Fu Wang; Fenglin Sun; Danyu Qin; Xi Wang; Bo Li; et al. (Journal of Meteorological Research, 2017)

Cancer risk from gaseous carbonyl compounds in indoor environment generated from household coal combustion in Xuanwei, China - Ka-Hei Lui; Wen-Ting Dai; Chi-Sing Chan; Linwei Tian; Bo-Fu Ning; Yiping Zhou; Xiaolin Song; Bei Wang; Jinwen Li; Jun-Ji Cao; Shun-Cheng Lee; Kin-Fai Ho (Environmental Science and Pollution Research, 2017)

CDK inhibitor SU9516 induces tetraploid blastocyst formation from parthenogenetically activated porcine embryos - Qing Guo; Long Jin; Hai-Ying Zhu; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Guang-Lei Zhang; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Jin-Dan Kang; et al. (Biotechnology Letters, 2017)

Knockdown of cardiac Kir3.1 gene with siRNA can improve bradycardia in an experimental sinus bradycardia rat model - Yang Li; Xiaodan Fu; Zhi Zhang; Bo Yu (Molecular and Cellular Biochemistry, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Elements in Fine Particulate Matter (PM $$_{2.5}$$ 2.5 ) from Indoor Air During Household Stoves Coal Combustion at Xuanwei, China - K. H. Lui; C. S. Chan; Linwei Tian; Bo-Fu Ning; Yiping Zhou; Xiaolin Song; Jinwen Li; Jun-Ji Cao; S. C. Lee; K. F. Ho (Aerosol Science and Engineering, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Early Cretaceous porphyry copper mineralization in Northeast China: the Changfagou example - Yong Zhang; Shu–Wen Xing; Chao Li; Shi–Fu Liang; Zheng–Tao Yu; Xiao–Hui Du; Yan Wang; Zeng–Jie Zhang; Yu–Bo Ma (International Geology Review, 2017)

Boundary-reflected waves and ultrasonic coda waves in rock physics experiments - Bo-Ye Fu; Li-Yun Fu; Wei Wei; Yan Zhang (Applied Geophysics, 2016)

Sensitivity of a regional climate model to land surface parameterization schemes for East Asian summer monsoon simulation - Wenkai Li; Weidong Guo; Yongkang Xue; Congbin Fu; Bo Qiu (Climate Dynamics, 2016)

Combination of antibiotics suppressed the increase of a part of ARGs in fecal microorganism of weaned pigs - Huizhi Li; Qingpo Chu; Feilong Xu; Lingling Fu; Tingting Liang; Yuan Li; Bo Zhou (Environmental Science and Pollution Research, 2016)

Characterization of the waxy gene in diploid Triticum L. and Aegilops L. species and its geographic distribution - Wei Li; Bang-Bo Fu; Zhe Li; Ya-Xi Liu; Zhi-En Pu; Peng-Fei Qi; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng (Genetic Resources and Crop Evolution, 2016)

Improvement and comparison of the rainfall–runoff methods in SWAT at the monsoonal watershed of Baocun, Eastern China - Qin-Bo Cheng; Christian Reinhardt-Imjela; Xi Chen; Achim Schulte; Xiang Ji; Fu-Lin Li (Hydrological Sciences Journal, 2016)

Antinociceptive effects induced by intra-lateral habenula complex injection of the galanin receptor 1 agonist M617 in rats - Li-Bo Fu; Ying Wang; Xiao-Xiao Sun; Xiao-Xia Liu; Ying Wang; Wen Zhuang (Experimental Brain Research, 2016)

Overexpression of d-amino acid oxidase from Bradyrhizobium japonicum, enhances resistance to glyphosate in Arabidopsis thaliana - Hongjuan Han; Bo Zhu; Xiaoyan Fu; Shuanghong You; Bo Wang; Zhenjun Li; Wei Zhao; Rihe Peng; Quanhong Yao (Plant Cell Reports, 2015)

Antiviral effect of lithium chloride on infection of cells by canine parvovirus - Pei Zhou; Xinliang Fu; Zhongshan Yan; Bo Fang; San Huang; Cheng Fu; Malin Hong; Shoujun Li (Archives of Virology, 2015)

Retraction Note to: Genetic polymorphisms in VDR, ESR1 and ESR2 genes may contribute to susceptibility to Parkinson’s disease: a meta-analysis - Zhan Gao; Hong-Juan Fu; Ju-Jun Xue; Zhi-Xuan Wu; Li-Bo Zhao (Molecular Biology Reports, 2015)

Isoprenaline induces epithelial–mesenchymal transition in gastric cancer cells - Yan-Jie Lu; Zhi-Jun Geng; Xiao-Yan Sun; Yu-Hong Li; Xiao-Bing Fu; Xiang-Yang Zhao; Bo Wei (Molecular and Cellular Biochemistry, 2015)

Elevated Serum Homocysteine (Hcy) Levels May Contribute to the Pathogenesis of Cerebral Infarction - Hong-Juan Fu; Li-Bo Zhao; Ju-Jun Xue; Zhi-Xuan Wu; Yue-Ping Huang; Wei Liu; Zhan Gao (Journal of Molecular Neuroscience, 2015)

Spatial distribution of heavy metal contamination in soils near a primitive e-waste recycling site - Sheng-Xiang Quan; Bo Yan; Fan Yang; Ning Li; Xian-Ming Xiao; Jia-Mo Fu (Environmental Science and Pollution Research, 2015)

EZH2-Induced H3K27me3 is Associated with Epigenetic Repression of the ARHI Tumor-Suppressor Gene in Ovarian Cancer - Yibing Fu; Jing Chen; Bo Pang; Chunyan Li; Jing Zhao; Keng Shen (Cell Biochemistry and Biophysics, 2015)

Association of PPARγ gene polymorphisms with osteoarthritis in a southeast Chinese population - DING ZHERU; FU PEILIANG; WU YULI; WU HAISHAN; QIAN QIRONG; LI XIAOHUA; ZHAO HUI; WANG BO; FU QIWEI (Journal of Genetics, 2014)

Identification and characterization of a novel phage display-derived peptide with affinity for human brain metastatic breast cancer - Bo Fu; Ying Zhang; Wei Long; Aifeng Zhang; Yafen Zhang; Yanli An; Fengqin Miao; Fang Nie; Mingli Li; Youji He; Jianqiong Zhang; Gaojun Teng (Biotechnology Letters, 2014)

Accumulation of FLT3+ CD11c+ dendritic cells in psoriatic lesions and the anti-psoriatic effect of a selective FLT3 inhibitor - Heng-Xiu Yan; Wei-Wei Li; Yan Zhang; Xia-Wei Wei; Li-Xin Fu; Guo-Bo Shen; Tao Yin; Xiu-Ying Li; Hua-Shan Shi; Yang Wan; Qing-Yin Zhang; Jiong Li; et al. (Immunologic Research, 2014)

Ectopic expression of Dendrobium EREB5 gene in Arabidopsis influences leaf morphology - Yuqiang Sun; Ying Shen; Anna Li; Wenfeng Fu; Yu Wang; Qicai Ying; Juan Hao; Brian Jones; Bo Shen; Huizhong Wang (In Vitro Cellular & Developmental Biology - Plant, 2014)

RETRACTED ARTICLE: Genetic polymorphisms in VDR, ESR1 and ESR2 genes may contribute to susceptibility to Parkinson’s disease: a meta-analysis - Zhan Gao; Hong-Juan Fu; Ju-Jun Xue; Zhi-Xuan Wu; Li-Bo Zhao (Molecular Biology Reports, 2014)

Sources and flows of embodied CO2 emissions in import and export trade of China - Yanmei Li; Jiafeng Fu; Zhanyun Ma; Bo Yang (Chinese Geographical Science, 2014)

Primordial follicle assembly was regulated by notch signaling pathway in the mice - Chun-Lei Chen; Xia-Fei Fu; Lin-Qing Wang; Jun-Jie Wang; Hua-Gang Ma; Shun-Feng Cheng; Zhu-Mei Hou; Jin-Mei Ma; Guo-Bo Quan; Wei Shen; Lan Li (Molecular Biology Reports, 2014)

Screening of multi-copy mannanase recombinants of Pichia pastoris based on colony size - Jia Zheng; Ning Guo; Fu-lai Lin; Li-shuang Wu; Hong-bo Zhou (World Journal of Microbiology and Biotechnology, 2014)

Alda-1 reduces cerebral ischemia/reperfusion injury in rat through clearance of reactive aldehydes - Si-Hai Fu; Hong-Feng Zhang; Zhong-Bao Yang; Ting-Bo Li; Bin Liu; Zheng Lou; Qi-Lin Ma; Xiu-Ju Luo; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Genetic variation in alkaloid accumulation in leaves of Nicotiana - Bo Sun; Fen Zhang; Guo-jun Zhou; Guo-hai Chu; Fang-fang Huang; Qiao-mei Wang; Li-feng Jin; Fu-cheng Lin; Jun Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Association of Serum Calcium and Hypertension Among Adolescents Aged 12–17 Years in the Rural Area of Northeast China - Hao Sun; Jingpu Shi; Hailong Wang; Lingyu Fu; Bo Zhou; Xiaomei Wu; Wei Dong; Hui Li; Wenli Wang (Biological Trace Element Research, 2013)

Expression of exoinulinase genes in Saccharomyces cerevisiae to improve ethanol production from inulin sources - Bo Yuan; Shi-An Wang; Fu-Li Li (Biotechnology Letters, 2013)

Factors underlying the association of body mass index with serum ALT in Chinese hypertensive adults without known hepatic diseases - Yan Zhang; Xian-hui Qin; Jian-ping Li; Yi-min Cui; Ze-yuan Liu; Zhi-gang Zhao; Jun-bo Ge; De-ming Guan; Jian Hu; Yan-ni Wang; Fu-min Zhang; Xin Xu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

RP105 involved in activation of mouse macrophages via TLR2 and TLR4 signaling - Bo Liu; Naisheng Zhang; Zhicheng Liu; Yunhe Fu; Shuang Feng; Shan Wang; Yongguo Cao; Depeng Li; Dejie Liang; Fengyang Li; Xiaojing Song; Zhengtao Yang (Molecular and Cellular Biochemistry, 2013)

Preparation and evaluation of a new releasable PEGylated tumor necrosis factor-α (TNF-α) conjugate for therapeutic application - ChuanYun Dai; Ya Fu; ShaoCheng Chen; Biao Li; Bo Yao; WanHong Liu; LiQing Zhu; Nan Chen; Ji Chen; Qiang Zhang (Science China Life Sciences, 2013)

Comparative transcriptome analysis of tobacco (Nicotiana tabacum) leaves to identify aroma compound-related genes expressed in different cultivated regions - Bo Lei; Xue-Hua Zhao; Kai Zhang; Jie Zhang; Wei Ren; Zhu Ren; Yi Chen; Hui-Na Zhao; Wen-Jie Pan; Wei Chen; Hong-Xun Li; Wen-Ya Deng; et al. (Molecular Biology Reports, 2013)

Exon 47 skipping of fibrillin-1 leads preferentially to cardiovascular defects in patients with thoracic aortic aneurysms and dissections - Wen-Jing Wang; Peili Han; Jun Zheng; Fang-Yuan Hu; Yun Zhu; Jin-Sheng Xie; Jian Guo; Zhe Zhang; Jie Dong; Gu-Yan Zheng; Huiqing Cao; Tian-Shu Liu; et al. (Journal of Molecular Medicine, 2013)

Salidroside attenuates inflammatory responses by suppressing nuclear factor-κB and mitogen activated protein kinases activation in lipopolysaccharide-induced mastitis in mice - Depeng Li; Yunhe Fu; Wen Zhang; Gaoli Su; Bo Liu; Mengyao Guo; Fengyang Li; Dejie Liang; Zhicheng Liu; Xichen Zhang; Yongguo Cao; Naisheng Zhang; et al. (Inflammation Research, 2013)

Optimization of fermentation process for the production of intracellular polysaccharide from Paecilomyces cicadae and the immuno-stimulating activity of intracellular polysaccharide - Jun-Wen Cheng; Yan-Bin Wang; Liang He; Hua Qian; Li-Zhong Fu; Hai-Bo Li (World Journal of Microbiology and Biotechnology, 2012)

Effects of fertilization and drought stress on tannin biosynthesis of Casuarina equisetifolia seedlings branchlets - Li Hua Zhang; Hong Bo Shao; Gong Fu Ye; Yi Ming Lin (Acta Physiologiae Plantarum, 2012)

Anomalous temperature–growth response of Abies faxoniana to sustained freezing stress along elevational gradients in China’s Western Sichuan Province - Zong Shan Li; Guo Hua Liu; Bo Jie Fu; Chan Juan Hu; Shu Zheng Luo; Xing Liang Liu; Fei He (Trees, 2012)

Partial antiviral activities of the Asn631 chicken Mx against newcastle disease virus and vesicular stomatitis virus - Bichun Li; Dezhi Fu; Yani Zhang; Qi Xu; Ligang Ni; Guobin Chang; Mengmeng Zheng; Bo Gao; Huaichang Sun; Guohong Chen (Molecular Biology Reports, 2012)

Analysis of 2,297 expressed sequence tags (ESTs) from a cDNA library of flax (Linum ustitatissimum L.) bark tissue - Song-Hua Long; Xin Deng; Yu-Fu Wang; Xiang Li; Rui-Qing Qiao; Cai-Sheng Qiu; Yuan Guo; Dong-Mei Hao; Wan-Qi Jia; Xin-Bo Chen (Molecular Biology Reports, 2012)

Spontaneous retroperitoneal hemorrhage after hemodialysis involving anticoagulant agents - Wen-xing Fan; Zheng-xu Deng; Fang Liu; Rong-bo Liu; Ling He; Bogati Amrit; Li Zang; Jing-wen Li; Xian-rong Liu; Song-min Huang; Ping Fu (Journal of Zhejiang University-SCIENCE B, 2012)

Identification of microRNA-like RNAs in a plant pathogenic fungus Sclerotinia sclerotiorum by high-throughput sequencing - Jiahong Zhou; Yanping Fu; Jiatao Xie; Bo Li; Daohong Jiang; Guoqing Li; Jiasen Cheng (Molecular Genetics and Genomics, 2012)

Construction and characterization of a normalized cDNA library from the river snail Bellamya aeruginosa after exposure to copper - Zi-Cheng Li; Li-Hui An; Qing Fu; Ying Liu; Lei Zhang; Hao Chen; Xing-Ru Zhao; Li-Jing Wang; Bing-Hui Zheng; Lin-Bo Zhang (Ecotoxicology, 2012)

Clinical Study of Autologous Cytokine-Induced Killer Cells for the Treatment of Elderly Patients with Diffuse Large B-Cell Lymphoma - Xue-chun Lu; Bo Yang; Rui-li Yu; Xiao-hua Chi; Shuai Tuo; Chao-wei Tuo; Hong-li Zhu; Yao Wang; Chao-guang Jiang; Xiao-bing Fu; Yang Yang; Yang Liu; et al. (Cell Biochemistry and Biophysics, 2012)

The Potential Influence of Seasonal Climate Variables on the Net Primary Production of Forests in Eastern China - Zong Shan Li; Guo Hua Liu; Bo Jie Fu; Jin Long Zhang (Environmental Management, 2011)

Analysis of variable sites between two complete South China tiger (Panthera tigris amoyensis) mitochondrial genomes - Wenping Zhang; Bisong Yue; Xiaofang Wang; Xiuyue Zhang; Zhong Xie; Nonglin Liu; Wenyuan Fu; Yaohua Yuan; Daqing Chen; Danghua Fu; Bo Zhao; Yuzhong Yin; et al. (Molecular Biology Reports, 2011)

A double-blind, placebo-controlled study of traditional Chinese medicine sarsasapogenin added to risperidone in patients with negative symptoms dominated schizophrenia - Shi-Fu Xiao; Hai-Bo Xue; Xia Li; Chao Chen; Guan-Jun Li; Cheng-Mei Yuan; Ming-Yuan Zhang (Neuroscience Bulletin, 2011)

Molecular characterisation of cereal cyst nematodes in winter wheat on the Huang-Huai floodplain of China using RFLP and rDNA-ITS sequence analyses - Bo Fu; Hong-xia Yuan; Yu Zhang; Xing-song Hou; Gao-lei Nian; Peng Zhang; Xiao-ping Xing; Bing-jian Sun; Ian T. Riley; Hong-lian Li (Australasian Plant Pathology, 2011)

Significant association of SNP rs2106261 in the ZFHX3 gene with atrial fibrillation in a Chinese Han GeneID population - Cong Li; Fan Wang; Yanzong Yang; Fenfen Fu; Chengqi Xu; Lisong Shi; Sisi Li; Yunlong Xia; Gang Wu; Xiang Cheng; Hui Liu; Chuchu Wang; et al. (Human Genetics, 2011)

Population variation of invasive Spartina alterniflora can differentiate bacterial diversity in its rhizosphere - Ming Nie; Le Xuan Gao; Jun Hong Yan; Xiao Hua Fu; Ming Xiao; Ji Yang; Bo Li (Plant Ecology, 2010)

Evaluation of genetic diversity in Lentinula edodes strains using RAPD, ISSR and SRAP markers - Li-Zhong Fu; Hong-Yu Zhang; Xue-Qian Wu; Hai-Bo Li; Hai-Long Wei; Qing-Qi Wu; Li-An Wang (World Journal of Microbiology and Biotechnology, 2010)

Chloroplast transformation of rapeseed (Brassica napus) by particle bombardment of cotyledons - Lin Cheng; He-Ping Li; Bo Qu; Tao Huang; Jin-Xing Tu; Ting-Dong Fu; Yu-Cai Liao (Plant Cell Reports, 2010)

Effects of moniliformin and selenium on human articular cartilage metabolism and their potential relationships to the pathogenesis of Kashin-Beck disease - An Zhang; Jun-ling Cao; Bo Yang; Jing-hong Chen; Zeng-tie Zhang; Si-yuan Li; Qiang Fu; Clare E. Hugnes; Bruce Caterson (Journal of Zhejiang University-SCIENCE B, 2010)

Combined Effects of Repeated Administration of 2,3,7,8-Tetrachlorodibenzo-p-dioxin and Polychlorinated Biphenyls on Kidneys of Male Rats - Chun-Feng Lu; Yi-Mei Wang; Shuang-Qing Peng; Li-Bo Zou; De-Hong Tan; Gang Liu; Ze Fu; Qiao-Xu Wang; Jing Zhao (Archives of Environmental Contamination and Toxicology, 2009)

Cloning and characterization of phosphorus starvation inducible Brassica napus PURPLE ACID PHOSPHATASE 12 gene family, and imprinting of a recently evolved MITE-minisatellite twin structure - Kun Lu; You-Rong Chai; Kai Zhang; Rui Wang; Li Chen; Bo Lei; Jun Lu; Xin-Fu Xu; Jia-Na Li (Theoretical and Applied Genetics, 2008)

Sustainability Evaluation of the Grain for Green Project: From Local People’s Responses to Ecological Effectiveness in Wolong Nature Reserve - Jian-Ying Xu; Li-Ding Chen; Yi-He Lu; Bo-Jie Fu (Environmental Management, 2007)

Relationships between O isotope equilibrium, mineral alteration and Rb–Sr chronometric validity in granitoids: implications for determination of cooling rate - Jiang Feng Chen; Yong-Fei Zheng; Zi-Fu Zhao; Bo Li; Zhi Xie; Bing Gong; Hui Qian (Contributions to Mineralogy and Petrology, 2007)

Purification and Characterization of a Cold-active Iron Superoxide Dismutase from a Psychrophilic Bacterium, Marinomonas sp. NJ522 - Zhou Zheng; Ying-Hui Jiang; Jin-Lai Miao; Quan-Fu Wang; Bo-Tao Zhang; Guang-You Li (Biotechnology Letters, 2006)

Eco-hydrological effects of landscape pattern change - Bo-Jie Fu; Wen-Wu Zhao; Li-Ding Chen; Zhan-Feng Liu; Yi-He Lü (Landscape and Ecological Engineering, 2005)